Spatio-temporal dynamics of honey bee–pathogen networks: Implications for colony health and productivity - Carlos Hernández-Castellano; María Martín-Domínguez; María Benito-Murcia; Eduardo J. García-Vicente; Ana Pérez-Pérez; Noelia Hermosilla; Martin Štrobl; Michal Knapp; Juan Manuel Alonso-Rodríguez; David Risco (Agriculture, Ecosystems & Environment, 2026)

Farmers' attitudes towards biodiversity shape the effectiveness of biodiversity-friendly management practices for wild bees, but not plants and spiders - Jeroen Scheper; David Kleijn; Fabian Klebl; Anneli Adler; András Báldi; Ignasi Bartomeus; Vincent Bretagnolle; J.P. Reinier De Vries; Sabrina Gaba; Maura Ganz; José M. Herrera; Felix Herzog; et al. (Biological Conservation, 2026)

Development of a quadruple isotope spiking methodology to study mercury methylation and methylmercury demethylation in environmental and biological media - Javier Garcia-Calleja; Pablo Rodríguez-González; Laura Suárez Criado; Emmanuel Tessier; João P. Santos; Sylvain Bouchet; Zoyne Pedrero; Vera I. Slaveykova; J. Ignacio García Alonso; David Amouroux (Analytica Chimica Acta, 2026)

Atmospheric organic nitrogen over the Iberian Peninsula: Patterns, sources, and implications - David Elustondo; Yasser Morera-Gómez; Raquel Ruiz-Checa; Carolina Santamaría; Héctor García-Gómez; Ignacio González-Fernández; Rocío Alonso; Anna Ávila; Esther Lasheras (Atmospheric Research, 2026)

Technological variability and raw material procurement in the Cantabrian Lower Magdalenian: Level G1 at El Cierro Cave (Ribadesella, Asturias, Spain) - Diego Herrero-Alonso; Sergio Martín-Jarque; Antonio Tarriño; David Álvarez-Alonso; Selina Delgado-Raack; Alejandro Prieto; Jesús F. Jordá Pardo; Esteban Álvarez-Fernández (Archaeological and Anthropological Sciences, 2026)
This paper presents a comprehensive analysis of the lithic assemblage from Level G1 of El Cierro Cave (northern Spain), attributed to the Cantabrian Lower Magdalenian. The study comprises 2,829 items, including 2,800 knapped artefacts, six macrolithic tools and 23 unmodified pebbles. Lithic procurement is dominated by flint, followed by quartzite and minor amounts of quartz. Eleven flint types have been identified, with local raw materials prevailing, while regional and tracer groups occur in lower proportions, indicating selective long-distance connections within the Basque-Cantabrian Basin. Technological analysis reveals complete operational chains for flake production using locally available resources, alongside greater variability in laminar reduction strategies. Blade production is limited and clearly subordinate to flake-oriented technologies. The retouched tool assemblage, dominated by endscrapers, conforms to typical Upper Palaeolithic techno-typological patterns, whereas backed bladelets are poorly represented. Use-wear analysis indicates a range of activities involving macrolithic tools, potentially linked to both lithic production and the processing of organic materials. Overall, the Level G1 assemblage at El Cierro is characterised by a strong reliance on local raw materials, restricted circulation of distant flints and low investment in laminar production, reflecting procurement strategies operating primarily at a local scale and a technological organisation adapted to domestic activities and reduced mobility.

The use of remote sensing to detect illegal, unreported, and unregulated (IUU) tuna fishing activities in the Peruvian Exclusive Economic Zone - Eizo Muñoz-Sovero; Ramzy Kahhat; Alejandro Deville; Diana Ita-Nagy; David Gonzales; Alonso Montero; Ian Vázquez-Rowe (Marine Policy, 2026)

Spatial distribution and seasonal dynamics of blue shark (Prionace glauca) and shortfin mako (Isurus oxyrinchus) catches from the Spanish surface longline fleet in the North Atlantic - José Carlos Báez; Alejandro Alegría; Julissa de la Rosa; Francisca Salmerón; Patricia Romero-Fernández; Davinia Torreblanca; María Lourdes Ramos-Alonso; José Francisco Moreno; David Macías (Regional Studies in Marine Science, 2026)

Analysis of sustainable printing materials using computed tomography and tensile testing for aeronautical applications - Claudia Alvarez; Diego Carou; David Álvarez; Eugenio López; Marcos Alonso (Journal of Cleaner Production, 2026)

Trends and risk factors of antimicrobial resistance of Neisseria gonorrhoeae in Catalonia, Spain, 2022–2023 - Mercè Herrero; Sonia Broner; Naiana Pastrana-Batalla; Eduard Anfruns; Evelin López-Corbeto; Victoria González; Judit Serra-Pladevall; Nieves Larrosa; Jacobo Mendioroz; Pilar Ciruela; Yuliya Poliakova; Mateu Espasa; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Towards Meaningful Learning in Analysis of Biomedical Signals and Systems through Google Colab Notebooks - Luz María Alonso-Valerdi; Juan Pablo Rosado-Aíza; Tania Yareni Pech-Canul; Paola Guadalupe Vázquez-Rodríguez; Luis Fernando Acosta-Soto; Mónica Sofía Mayorga-Constantino; Roberto David Guajardo-Reyna (Biomedical Engineering Education, 2026)

OC7 phase I: CFD investigation of viscous forces on rectangular members of semisubmersibles - Yingqian Liao; Lu Wang; Amy Robertson; Jason Jonkman; Arjen Koop; Guillén Campaña-Alonso; Daniele Aromatario; António Maximiano; Hannah Darling; David P. Schmidt; Shengbai Xie; Jasim Sadique; et al. (Ocean Engineering, 2026)

Species-specific growth models inform sustainable management of Rhizophora mangle in the Colombian Caribbean - David Valderrama; Jaime Polanía; Valeria Aguirre; Sergio Alonso Orrego (Wetlands Ecology and Management, 2026)
Mangrove ecosystems provide crucial ecological services but face threats from climate change and unsustainable resource use. This highlights the need for science-based forest management initiatives. Cispatá Bay, located in the Colombian Caribbean, hosts the country’s only mangrove under a regulated sustainable use model. Yet, current management guidelines rely on generalized silvicultural criteria, such as a uniform minimum logging diameter (MLD) of 10 cm and a 14 year cutting cycle (CC), which do not reflect species-specific growth dynamics, potentially compromising sustainability. This study aims to improve sustainable forest management in Cispatá Bay by developing species-specific growth models for Rhizophora mangle , a dominant and heavily harvested species. We introduce a novel methodological framework for sustainable forest management in mangrove ecosystems, integrating dendrochronology and biometric modeling to derive ecological management parameters. We combined tree-ring data from 26 dead individuals with forest inventory measurements and applied nonlinear mixed-effects modeling, accounting for autocorrelation and growth eccentricity. The resulting models yielded biologically meaningful ontogenetic traits, including a maximum mean diameter (A max ) of 40.35 cm, a weighted average growth rate (WAGR) of 0.42 cm year⁻ 1 , a lifespan (t span ) of 95.12 years, and a halflife (t 0.5 ) of 41.09 years. Additionally, we estimated an MLD of 24 cm and a CC of 20 years—both substantially higher than current thresholds. These findings suggest that continued application of generalized metrics may compromise forest regeneration, reduce volume recovery, and undermine long-term sustainability. By integrating dendrochronological techniques with biometric modeling, this research provides a replicable framework for evidence-based forest governance in mangroves.

Acute effects of anodal transcranial direct current stimulation on maximal voluntary force, repeated maximal isometric contractions and corticospinal excitability in healthy young adults - David Colomer-Poveda; Irene Mera-González; Daniel Marcos-Frutos; Luna Botana-López; José Andrés Sánchez-Molina; Virginia López-Alonso; Gonzalo Márquez (European Journal of Applied Physiology, 2026)

Comparison of solid phase microextraction coatings for headspace extraction of volatile perfluoroalkyl substances using one-dimensional and comprehensive two-dimensional gas chromatography - Madison L. Williams; Aethena Fitzgerald; David Alonso; Joe Binkley; John Hayes; Michael Stebler; Emanuela Gionfriddo (Analytica Chimica Acta, 2026)

High Densities of Large Herbivores Rapidly Disrupt Ecosystem Integrity - Jorge Isla; Emmanuel Serrano; Juan A. Calleja; Carlos Hernández‐Castellano; Rafael Alcalá‐Herrera; Elena Albanell; Carlos Alonso; Elena Baraza; Matthew Brolly; Niall Burnside; Ana Burón‐Ugarte; Miquel Capó; et al. (Global Change Biology, 2026)
Human‐induced high densities of large wild herbivores may pose a threat to natural ecosystems, modifying biodiversity and ecosystem functioning. Although the negative impacts on individual taxa and processes are well documented, a comprehensive understanding of how ecosystem integrity responds to high herbivore densities remains limited. This study addresses this gap through an extensive herbivore‐density manipulation experiment conducted in two Mediterranean woodlands. We established two scenarios of high red deer ( Cervus elaphus ) density, representative of some protected areas (~30 individuals·km 2 ) and intensively managed hunting estates (~90 individuals·km 2 ). We monitored 38 metrics encompassing a broad spectrum of biodiversity and functional responses to synthesize the short‐term impacts of high herbivore densities. We revealed an overall 13% decline in ecosystem integrity after one year of exposure to high herbivore densities, with particularly widespread impacts on functional responses and detrimental effects on biodiversity components. We detected rapid declines in plant diversity and a positive response of epigeic invertebrate orders. Conversely, ants (analyzed separately), birds, and small mammals remained mostly unaffected. Functional responses were consistently impaired, including declines in plant regeneration and physiological performance, simplified pollination networks, degraded soil structure, and increased disease vectors. These findings show that human‐induced high herbivore densities rapidly create conditions that disrupt ecosystem integrity, reveal early signs of ecological degradation, and underscore the urgent need for population regulation.

Dual role of ascorbyl Palmitate as coagel and adjuvant in experimental antivenom development - Franco M. Maslovski; Sofía G. Brignone; Bruno Barrientos; David R. Hernández; María del Rosario Alonso; Gisela L. Lopez; Gonzalo A. Ojeda; Felicitas Peyrano; Ana M. González; Santiago D. Palma; Laura C. Leiva; Maletto Belkys; et al. (Drug Delivery and Translational Research, 2026)

Hydrogeochemical modeling strategies and geophysical–geological integration to identify geogenic and anthropogenic processes in a metamorphic basement aquifer - Berenice Gómez-Mena; Janete Morán-Ramírez; José Alfredo Ramos-Leal; David Ernesto Torres Gaytán; Briseida López-Álvarez; Isaac Bonola-Alonso; Manuel Martínez-Morales (Science of The Total Environment, 2026)

Production of precursors for sustainable aviation fuels through furfural/cyclopentanone aldol condensation boosted by TiO2-loaded dendritic ZSM-5 catalysts - Daniel de la Calle; Jennifer Cueto; María del Mar Alonso-Doncel; Rafael A. García-Muñoz; David P. Serrano (Fuel, 2026)

Bearing the heat: Forest cover and human disturbance mediate brown bear behavior under thermal stress - Pablo Cisneros-Araujo; David Cubero; Daniel Pinto; Pablo Salinas; Francisco Jiménez; Javier García; Rebeca Martín; Víctor Salvador; Carlos Alonso; Daniel Gambra; Juan Ignacio García-Viñas; Aitor Gastón; et al. (Biological Conservation, 2026)

Climate and farming system dominate wheat yield responses across European pedoclimatic zones, despite widespread soil nutrient surpluses - Manuel Conde-Cid; Paula Pérez-Rodríguez; Andrés Rodríguez-Seijo; Manuel Arias-Estévez; Antía Gómez-Armesto; Flora Alonso-Vega; Juan Carlos Nóvoa-Muñoz; Claudia Campillo-Cora; Vanesa Santás-Miguel; María J. I. Briones; Irene Ollio; Eva Lloret; et al. (Plant and Soil, 2026)
Background and aims European wheat production faces the challenge of maintaining yields while reducing environmental impacts from agrochemicals. Organic farming is often considered a sustainable alternative to promote soil health and reduce chemical inputs. This study assessed nutrient status in wheat soils across nine European pedoclimatic zones, comparing conventional and organic systems and evaluating management practices such as crop rotation, tillage and fertilization type. Methods A total of 188 soils were analyzed for macro- and micronutrients, and wheat yield data were evaluated in relation to soil nutrients, climate, wheat type (winter- vs. spring-sown), and management using correlation, random forest, and regression analyses. Results Soils showed excess P, K, Mg, Cu, Fe, Mn, and Zn, but S and B deficiencies. Organic systems increased total N, while conventional farming enhanced nitrate, sulfate, and boron. Wheat yield was primarily driven by temperature, precipitation, wheat type (winter- vs. spring-sown), and farming system, with additional contributions from fertilization and nutrients (particularly exchangeable Ca, Fe, Mn, and Zn). On average, organic yields were 37% significantly lower than conventional, but these differences were smaller in Mediterranean zones due to reduced pest pressure and improved water retention and infiltration. Practices such as crop rotation, residue incorporation, and reduced tillage positively influenced yield. Conclusion Organic farming supports soil health and sustainable use of resources, but may reduce wheat yield in northern and central European pedoclimatic zones. Tailored nutrient management combined with agronomic practices can enhance productivity while minimizing environmental impacts, especially in climate-stressed regions.

Mapping Escolar ( Lepidocybium flavobrunneum ) in Motion: Oceanographic Forces Shaping Its Habitat in the Southwestern South Atlantic, With Insights From Fishers' Perceptions - Lucas Rodrigues; Maria Grazia Pennino; Paul Gerhard Kinas; David Conesa; Alba Fuster‐Alonso; Andrés Domingo; Rodrigo Forselledo; Federico Mas; Bruno Mourato; Rodrigo Sant'Ana; Vinni Santos Thykjaer; Raquel Virginia Marquez Marquez; et al. (Fisheries Oceanography, 2026)
Lepidocybium flavobrunneum [Smith, 1843], commonly known as escolar, is a large pelagic species, important for global and local fisheries, particularly in the southwestern South Atlantic Ocean (SWAO), where it constitutes a significant portion of the catch. However, despite its important socioeconomic role, it remains less studied compared to other large pelagic species. Enhancing research efforts is therefore key to better understanding the ecological processes that influence its spatial and temporal distribution. To address this gap, our study applied species distribution models (SDMs) to escolar's occurrence and abundance using longline fleet data from south Brazil and Uruguay. Estimation and prediction were conducted at the Bayesian framework using the integrated nested Laplace approximation (INLA) methodology combined with the stochastic partial differential equation (SPDE) approach. Our findings reveal a strong correlation between warmer sea surface temperatures and increased escolar occurrence and abundance in the SWAO, particularly during the austral summer, in contrast to cooler‐season patterns observed elsewhere. Escolar's distribution is influenced by the southward and westward movement of seawater driven by the Brazil Current, and its preference for depths greater than 2000 m reflects its oceanic nature. Predicted areas of higher abundance around the continental slope (between 33° and 37° S) and the Rio Grande Rise are linked to the dynamic interaction of warm and cold currents and nutrient‐rich waters. Additionally, escolar's sensitivity to low‐light conditions may explain reduced catches during moonlit nights. A complementary analysis assessing the synergistic influence of sea surface temperature and lunar illumination on escolar occurrence indicated that, under high temperatures (> 22 °C), occurrence is further enhanced during dark nights. Furthermore, semi‐structured interviews with vessel captains revealed that 90% identified temperature (via open‐ended responses) as a key environmental factor driving escolar catches, and 80% of them attributed a strong influence (greater than average catch rates) to temperature, summer season and new moon phase. This study provides new insights into escolar's seasonal and spatial patterns, emphasizing the impact of oceanographic features and light conditions on its distribution. It also highlights the need for further research into the mechanisms driving escolar populations.

The BK channel interactome: molecular partnerships and biophysical implications - Nadya Yanes-Alonso; Bárbara Armas-Rijo; Andrea Reyes-Carrión; Rebeca Navarro-Alonso; Luis O. Romero; David Bartolomé-Martín; Teresa Giraldez (Biophysical Reviews, 2026)
Large conductance voltage- and Ca 2 ⁺-activated K⁺ (BK) channels are key regulators of membrane excitability and intracellular Ca 2 ⁺ signaling in a wide range of excitable and non-excitable cells. Although the biophysical properties of BK channels have been extensively characterized, it has become increasingly clear that their functional diversity arises largely from interactions with a broad network of associated proteins. In this focused review, we provide an updated overview of the BK channel protein interactome, highlighting how these interactions shape channel gating, trafficking, localization, and coupling to Ca 2 ⁺ sources. We discuss well-established regulatory partners, including β and γ auxiliary subunits, as well as emerging modulators such as BKIP-1 and LINGO-1. We further examine interactions with cytoskeletal and trafficking proteins that govern BK channel surface expression and mobility, and with Ca 2 ⁺-permeable channels and receptors, including voltage-gated Ca 2 ⁺ channels, TRP channels, ryanodine receptors, IP₃ receptors, and NMDA receptors, that create specialized Ca 2 ⁺ signaling nanodomains. Finally, we summarize the roles of intracellular signaling molecules and scaffolding proteins that integrate BK channels into larger signaling assemblies. Together, these findings position BK channels as central hubs within multiprotein complexes that enable precise, context-dependent control of cellular excitability and Ca 2 ⁺-dependent physiological processes.

Assessing whale-watching compliance: A replicable framework for international–national correspondence in continental America - David Alonso Rosales-Chapula; César Augusto Salinas-Zavala; Marco Antonio Almendarez-Hernández; Cristina González-Rubio Sanvicente; José Alberto Zepeda-Domínguez; María Verónica Morales-Zárate (Regional Studies in Marine Science, 2026)

Isomerization of α- and β-pinene epoxides over dendritic ZSM-5 zeolites - Carina Mosquera; Luis A. Gallego-Villada; Marta Mediavilla; Jennifer Cueto; Maria del Mar Alonso-Doncel; Edwin Alarcón; David P. Serrano (Chemical Engineering Journal, 2026)

Understanding Mosquito Vector Invasion Pathways: Synergistic Effects of Human Mobility, Climate and Natural Dispersal - Marta Pardo‐Araujo; Egor Kotov; David Alonso; Frederic Bartumeus (Ecology Letters, 2026)
Mosquito‐borne diseases are rising globally, driven in part by the expanding range of invasive vector species. However, the mechanisms underlying their spread remain poorly understood, largely due to limited and inconsistent data. Here, we integrate high‐resolution human mobility data with a thermo‐biologically realistic metapopulation model to investigate the colonisation dynamics of the dengue vector, Aedes albopictus , using 20 years of invasion data from Spain. Our results reveal the dual role of humans: as architects of climate change, making local environments increasingly suitable, and as vehicles of dispersal, inadvertently transporting this vector across regions. The spread occurs through a fragmented human mobility network, while natural dispersal bridges gaps between connected areas, enabling faster and more continuous expansion. These findings underscore the importance of considering the synergistic effects of climate, human movement, and natural dispersal when forecasting future range expansions and designing coordinated, multi‐scale vector control strategies in an era of rapid environmental change.

Occurrence and ecological risk of pesticides in water and sediments in regions with intensive agricultural activities - Endi Adriano Fures; Rafaela Roberta Morelato; Alonso Moscon; Laila Barcelos; Miqueias de Castro da Silva; Lisiane Martins Volcão; Jonas Simon Dugatto; David Augusto Reynalte Tataje; Liziara da Costa Cabrera (Environmental Science and Pollution Research, 2026)

Characterization of metal contaminants in the Critically Endangered angelshark (Squatina squatina): A first ecotoxicological insight - Tomas Bañeras; David Jiménez-Alvarado; Eva K.M. Meyers; Hector Toledo-Padilla; Arturo Hardisson; Dailos Gonzalez-Weller; Joanna Barker; Lucy R. Mead; Ana Espino-Ruano; Ayoze Castro-Alonso; María José-Caballero; Ángel Gutiérrez (Marine Pollution Bulletin, 2026)

Functional characterization of splice variants in hereditary breast and ovarian cancer susceptibility genes - Laura Rosado-Jiménez; Younes Mestre-Terkemani; Ángeles García-Aliaga; María D. Sarabia-Meseguer; Miguel Marín-Vera; José A. Macías-Cerrolaza; Pilar Sánchez-Henarejos; María R. García-Hernández; Marta Zafra-Poves; Beatriz C. Álvarez-Abril; Carmen B. López-Sánchez; María P. Moya-Martínez; et al. (Familial Cancer, 2025)

Transformation of BTEX compounds emitted by aircraft engines at ground level - Jesús Rodríguez-Maroto; Rosa Pérez-Pastor; Susana García-Alonso; Enrique Rojas; David Sanz; Imara Ibarra; Manuel Pujadas; Dévora Hormigo; Jesús Sánchez; Paola Moreno; María Sánchez; Mark Johnson (Environmental Science and Pollution Research, 2025)
Volatile organic compounds, such as benzene, toluene, ethylbenzene and xylenes (BTEX) are emitted during the various aviation activities at ground level, such as take-off, approach and taxiing, that take place at or near airports. In addition to causing adverse health effects, these compounds are precursors of secondary aerosols (SOAs). The expected growth in air traffic in the near future makes it necessary to anticipate and control these emissions. As part of the AVIATOR project (EU Horizon2020), gaseous samples were collected in sorbent tubes and analysed by GC/MS, including emissions of commercial aircraft engines and airport ambient air, to study the evolution and transformation of BTEX. Three sites were selected: the INTA aircraft engine test cell, Ciudad Real and Madrid-Barajas airports. PM was collected on filters and substrates and analysed gravimetrically, with three different samplers: high-volume air sampler, Berner low pressure impactor, and an automated off-line sampler developed by CIEMAT. The ground idle configuration that simulates taxiing manoeuvres (before take-off and after landing) has been identified as a critical contributor to BTEX emissions at airports, with a concentration of over 460 ng L −1 . Benzene is consistently emitted at higher levels than toluene and the emission of both increases with engine acceleration. In the plume, dilution with air decreases not only the concentration of BTEX, but also the prevalence of the compounds, making benzene no longer the dominant compound. Variations in diagnostic ratios and meteorological conditions, as well as sensitivity parameters to PM concentration, may suggest physicochemical transformation of BTEX into SOAs.

Inhibitory effects of 6-O-palmitoyl-l-ascorbic acid (ASC16) on the enzymatic activity of Bothrops alternatus venom - Franco Maslovski; Jaime Andrés Pereañez; David Hernández; María Alonso; Silvina Echeverría; Carolina Gay; Laura Leiva; Emilio Angelina; Luciano Fusco (Archives of Toxicology, 2025)

Alarming conservation status of Western European steppe birds and their habitats: An expert-based review of current threats, traits and knowledge gaps - Julia Gómez-Catasús; Ana Benítez-López; Mario Díaz; David González del Portillo; Cristian Pérez-Granados; Juan Carlos Alonso; Beatriz Arroyo; Inmaculada Abril-Colón; Adrián Barrero; Rafael Barrientos; Luis Bolonio; Gerard Bota; et al. (Biological Conservation, 2025)

Acute caffeine intake improves muscular strength, power, and endurance performance, reversing the time-of-day effect regardless of muscle activation level in resistance-trained males: a randomized controlled trial - Juan Jesús Montalvo-Alonso; Marta del Val-Manzano; Ester Cerezo-Telléz; Carmen Ferragut; David Valadés; Javier Rodríguez-Falces; Alberto Pérez-López (European Journal of Applied Physiology, 2025)
Introduction This study examined the effects of acute caffeine intake on muscular electrical activity during strength, power, and endurance performance tests at different times of day in bench press and back squat exercises. Methods Thirteen resistance-trained men participated in a triple-blind, cross-over, randomized controlled trial with four conditions: (a) morning with caffeine, (b) morning with placebo, (c) evening with caffeine, and (d) evening with placebo. Trials were conducted at 9:00 AM and 6:00 PM, with participants consuming caffeine or placebo (3 mg/kg) 60 min prior. Muscular strength/power was tested at 25%, 50%, 75%, and 90% one-repetition maximum (1RM) for bench press and back squat, while muscular endurance was assessed at 65% 1RM through a set-to-failure. Surface electromyography (EMG) measured muscle electrical activity. Results In muscular strength/power tests, caffeine increased mean velocity (V mean ) and power output (W mean ) in the back squat at 75% (P = 0.012–0.001, g = 3.84–2.71) and 90%1RM (P = 0.043–0.009, g = 2.77–2.46) in both morning and evening trials. At 25%1RM, caffeine counteracts morning performance decline in bench press (10–11%, P = 0.001, g = 2.62–1.68) and back squat (8–11%, P = 0.010–0.003, g = 2.22–1.64). In muscular endurance tests, caffeine increased V mean and W mean in bench press in the morning (11–12%, P = 0.003–0.005, g = 2.55–1.89) and back squat in both morning and evening trials (6–9%, P = 0.001–0.027, g = 2.79–1.73). EMG activity remained unchanged in all conditions. Conclusions Acute caffeine intake enhances muscular strength/power at moderate-to-high loads (75%- 90%1RM) and endurance performance (65%1RM) in the back squat while counteracting morning declines at light-load (25%1RM) for both exercises without altering muscle electrical activity.

Revealing Chronotypes Across Aquatic Species Using Acoustic Telemetry - Martina Martorell‐Barceló; David Abecasis; Mourad Akaarir; Alexandre Alonso‐Fernández; Robert Arlinghaus; Eneko Aspillaga; Margarida Barcelo‐Serra; Niels W. P. Brevé; Jan G. Davidsen; Antoni Gamundí; Amalia Grau; Bernat Hereu; et al. (Fish and Fisheries, 2025)
Acoustic telemetry offers valuable opportunities to investigate individual variability in circadian‐related and other behaviours and how environmental cues shape these patterns in wild fish populations. However, this potential has not yet been fully exploited. We conducted a meta‐analysis on 44 datasets from 34 distinct marine and freshwater species and different types of data (acoustic detections, depth, acceleration and positioning). Our aim was to explore the potential of acoustic telemetry in identifying chronotypes as consistent among‐individual differences in circadian‐related behaviours. First, we applied hidden semi‐Markov models to classify individual time series into active and rest states. Subsequently, we computed two classical circadian‐related behavioural traits: awakening time (as the activity onset) and rest onset (as the activity offset). Subsequently, we identified distinct phenotypes by decomposing behavioural variation into within‐ and among‐individual components based on repeatability scores. We found evidence of distinct chronotypes in 17 species, with average repeatability scores of 0.52 for awakening time and 0.43 for rest onset, revealing that chronotypes are common in aquatic species. Our findings highlight that both the data type, particularly acceleration sensors, and the number of detections are effective tools for exploring chronotypes. Our study proposes a novel approach to characterising daily activity patterns in aquatic species, predominantly in fishes, and provides guidelines for investigating chronotypes across diverse taxa. We emphasise the promise of biotelemetry and advanced statistical models for improving our understanding of the behaviour of aquatic species and highlight the value of synthesising across large data sets collected in networks of biotelemetryprojects.

Evaluation of Combined Use of Protein and Postbiotics Feed Supplements in Honey Beehives in Autumn and Spring - Eduardo J. García-Vicente; María Benito-Murcia; María Martín; Ana Pérez; Noelia Hermosilla; Juan Manuel Alonso; David Risco (Probiotics and Antimicrobial Proteins, 2025)
Feed supplementation in beehives is a commonly necessary practice in beekeeping today, to address the many risks the honey bees face, mainly the climate change and times of food scarcity, agricultural pesticides, or pathogens such as Varroa destructor or Nosema ceranae . Protein supplements and postbiotics products have been evaluated in beehives feed, obtaining improvements of the strength and sanitary status, but they have not been tested in combination. In this study, two experiences have been carried out in autumn and spring to check the potential beneficial effect of this combination in the beehives. Two monitoring were carried out, before and after 1 month of the application of products, in order to assess the strength (number of bees, amount of brood, brood survival, and pollen/honey reserves) and sanitary status ( V. destructor and N. ceranae infestation levels) of the colonies. Firstly, the results obtained in autumn experience showed a reduction of both pathogens in supplemented group. On the other hand, in spring, the combination of protein and postbiotics enhanced the brood survival and honey yield, and decreased the V. destructor infestation. Thus, the combined use of protein and postbiotics as feed supplements could be an important tool to improve the sanitary status after the cold season, and to increase the strength and production of beehives in spring, unifying the benefits of both supplements.

Genetic parameters of fiber density traits and their relationship with textile traits in alpacas - Alan Cruz; Edgar Quispe; Alex Yucra; Renzo Morante; Alonso Burgos; Max David Quispe; Juan Pablo Gutiérrez; Gustavo Gutiérrez-Reynoso (Livestock Science, 2025)

Insights Into Pandemic and Post-Pandemic Dynamics of Enteric Viruses in a Middle-Size City—Burgos, Spain—Using a Long-Term Wastewater Surveillance - Lorena Casado-Martín; Marta Hernández; Daniel Pérez-Alonso; Nadine Yeramian; Mariana Alves-Elois; Rafael Dorighello-Cadamuro; Gislaine Fongaro; José María Eiros; David Rodríguez-Lázaro (Food and Environmental Virology, 2025)

A Comprehensive Database of Expert‐Curated Occurrences for the Genus Carex L. (Cyperaceae) - María Sanz‐Arnal; Pablo García‐Moro; Carmen Benítez‐Benítez; Marina Coca‐de‐la‐Iglesia; Angélica Gallego‐Narbón; Consolación Barciela; Fabrizio Bartolucci; Prabin Bhandari; Matthew Bradley; Asunción Cano; Antoine Derouaux; Sabina Donadío; et al. (Global Ecology and Biogeography, 2025)
Motivation Geographic occurrences are essential for biodiversity studies, but publicly available repositories like GBIF often contain errors and biases, especially for taxonomically complex groups like Carex L. (Cyperaceae). This work provides an expert‐curated global dataset of occurrences compiled from different sources to enhance data accuracy and usability. The final dataset includes 384,067 occurrences of 1790 Carex species. Main Types of Variables Contained The dataset includes species occurrence records with geographic coordinates, taxonomic identifications, and curation flags (e.g., introduced, erroneous records). Spatial Location and Grain The dataset covers a global scale, using the WGS84 projection. Spatial resolution is standardised to a minimum of three decimal degrees (~1 km, if possible). Time Period and Grain Online records span from 1950 to 2020, but some manually georeferenced records are earlier (1850). There is also fieldwork data after 2020, specifically up to 2023. Major Taxa and Level of Measurement Cyperaceae: Carex . Most records have species‐level identification, and some of them are identified at subspecies or variety levels. Software Format Data are supplied as comma‐separated values files with UTF‐8 encoding.

Body mass index and prognosis of infective endocarditis - Raquel Frías-García; Patricia Muñoz García; Marina Machado Vilchez; Gregorio Cuerpo Caballero; Raquel Rodríguez-García; M Ángeles Rodríguez-Esteban; M Carmen Fariñas-Álvarez; José M. Miró Meda; Andrea Gutiérrez Villanueva; Guillermo Ojeda-Burgos; Ane Josune Goikoetxea-Agirre; Marina Bernal Palacios; et al. (Infectious Diseases, 2025)

Neanderthal mobility over very long distances: The case of El Castillo cave (northern Spain) and the ‘Vasconian’ Mousterian - Diego Herrero-Alonso; José-Manuel Maíllo-Fernández; Natalia Abellán-Beltrán; Macarena Moral; Irene González-Molina; Irene Solano-Megías; Sofía Luzón-Ruiz; Juan Marín; Adrián Álvarez-Vena; David Martín-Perea; Ana Neira; Federico Bernaldo de Quirós; et al. (Journal of Human Evolution, 2025)

Are abandoned mine tailings a valuable resource for recovering Rare Earth Elements? Life cycle assessment and cost analysis - Martín Muñoz-Morales; David Sanchez-Ramos; Hassay L. Medina-Díaz; Francisco J. López-Bellido; Jacinto Alonso-Azcárate; Francisco J. Fernández-Morales; Luis Rodríguez (Journal of Cleaner Production, 2025)

Pesticide residues in beeswax from Western Spain: Toxicological risk for bee health and beekeeping productivity - María Benito-Murcia; Eduardo García-Vicente; María Martín; Ana Pérez; David Risco; Juan Manuel Alonso Rodríguez; Francisco Soler; Marcos Pérez-López; María Prado Míguez-Santiyán; Salomé Martinez-Morcillo (Environmental Toxicology and Pharmacology, 2025)

More than a fingerprint on a pebble: A pigment-marked object from San Lázaro rock-shelter in the context of Neanderthal symbolic behavior - David Álvarez-Alonso; M. de Andrés-Herrero; Andrés Díez-Herrero; S. Miralles-Mosquera; M. C. Sastre Barrio; M. Á. Maté-González; E. Nieva Gómez; M. R. Díaz Delgado; E. Ruiz Mediavilla (Archaeological and Anthropological Sciences, 2025)
The pebble discovered in the San Lázaro rock-shelter (Segovia, Central Spain) is the oldest known non-utilitarian object with a fingerprint made in Europe. Its morphology and the strategic position of an ocher dot, where a dermatoglyphic image has been detected, may be evidence of symbolic behavior. This object contributes to our understanding of Neanderthals’ capacity for abstraction, suggesting that it could represent one of the earliest human facial symbolizations in Prehistory. All the analyses carried out suggest an intentional effort to transport and paint the pebble for non-utilitarian purposes, suggesting that it is indeed the work of Neanderthals. The discovery is doubly exceptional because it includes the most complete dermatoglyphic image identified to date, with the exception of the partial fingerprint from Königsaue, both with a comparable minimum age. This dermatoglyphic image is not visible and it was revealed after a multispectral analysis. This method adds significant value to the identification that has been carried out of the human fingerprint, as it is the first time that such an analysis has been conducted with evidence as ancient as this, opening the door to future research and discoveries.

Changes in lithic raw material and technological management during the Mesolithic: a view from El Mazo (Northern Iberia) - Diego Herrero-Alonso; Natividad Fuertes-Prieto; Antonio Tarriño; David Cuenca-Solana; Asier García-Escárzaga; Jorge Calvo-Gómez; Igor Gutiérrez-Zugasti (Archaeological and Anthropological Sciences, 2025)
This study investigates the lithic industry at the Mesolithic shell midden site of El Mazo (Andrín, Asturias), on the Asturian coastline in Northern Iberia, focusing on resource management, production strategies, and mobility patterns of the last hunter-gatherer-fishers. El Mazo provides a unique opportunity to examine lithic resource use across the Early-Middle Holocene transition, with a particular emphasis on the dynamic of the 8.2 ka climate event. Raw material analysis reveals that most lithic resources originated locally (

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

Biomonitoring toxic and essential element accumulation in trout in the as pontes mine pit lake (NW Spain) - Marta López-Alonso; Marta Miranda; Inmaculada Orjales; Víctor Pereira; Belén Larrán; Ruth Rodríguez-Bermúdez; Cathaysa Veiras; Álvaro Robles; David Bravo; Ricardo Juncosa; Carlos Herrero-Latorre (Chemosphere, 2025)

Green covers effectively increase arthropod biodiversity in orchards, even at high management intensity - Remco Ploeg; Alberto Rodriguez Ballesteros; Ignasi Bartomeus; David Kleijn; Jeroen Scheper; Elena Velado Alonso (Agriculture, Ecosystems & Environment, 2025)

A Two-Decade Overview of the Environmental Carrying Capacity in Bahía Santa Maria–La Reforma Coastal Lagoon System - Omar Calvario-Martínez; Julio Medina-Galvan; Virginia P. Domínguez-Jiménez; Rosalba Alonso-Rodríguez; Miguel A. Sánchez-Rodríguez; Paulina M. Reyes-Velarde; Miguel Betancourt-Lozano; David Serrano-Hernández (Journal of Marine Science and Engineering, 2025)
Santa María Bay–La Reforma (SMBLR), with its 58,300 ha is one of Mexico’s most extensive estuarine lagoon systems. It is made up of islands, estuaries, and mangrove areas, which provide a vital part of the habitat and refuge of a significant number of birds, fish, amphibians, reptiles, and mammals. The fishing of blue and brown shrimp, marine and estuarine fish, as well as the exploitation of crab and bivalve mollusks, represent an important economic value for the communities that live there and for the state of Sinaloa, Mexico. This state ranked second in fisheries production and first in aquaculture production by 2023. However, the biological richness of this ecosystem has historically been threatened by economic activities such as agriculture, livestock, and aquaculture that, via watersheds, translate into continuous inputs of nutrients and other pollutants. This has led to modifications to the system such as changes in the structure of pelagic and benthic communities, mainly in response to eutrophication. To understand the dynamics of nutrient inputs to the ecosystem, this work presents a comparative analysis of the system’s carrying capacity and the magnitude of the main economic activities from 2007 to 2019. We found that during each season of the year and its transitions, the system functions as a nitrogen and phosphorus sink, which is associated with autotrophic net ecosystem metabolism and nitrogen fixation processes. We suggest that while water residence times in SMBLR are short, these are strongly influenced by the high volumes of water and nutrient loads determined by the spatio-temporal variations in hydrological drainage from the basins of influence of the system. The discharge of agriculture and aquaculture drains into SMBLR are areas of concern due to the high amount of nutrients. Although SMBLR is mostly an autotrophic system, there are signs that the carrying capacity during some seasons has been exceeded, and adverse ecological and socioeconomic effects in the basin are evident.

Unraveling the interplay between humans and carnivores in El Olivo Cave during the Middle and Upper Paleolithic period (Llanera, Asturias, Spain) - Clara Mielgo; José Yravedra Sainz de los Terreros; David Álvarez-Alonso; María de Andrés-Herrero; Aitor Hevia-Carrillo (Geobios, 2025)

Enhanced production of jet fuel precursors via furfural/cyclopentanone aldol condensation by synergistic pairing TiO2 with nano-ZSM-5 zeolite - Jennifer Cueto; Daniel de la Calle; María del Mar Alonso-Doncel; Elena A. Giner; Rafael A. García-Muñoz; David P. Serrano (Bioresource Technology, 2025)

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Potential Spatial Mismatches Between Marine Predators and Their Prey in the Southern Hemisphere in Response to Climate Change - Maria Bas; Jazel Ouled‐Cheikh; Alba Fuster‐Alonso; Laura Julià; David March; Francisco Ramírez; Luis Cardona; Marta Coll (Global Change Biology, 2025)
Global change is rapidly reshaping species' habitat suitability ranges, hence leading to significant shifts in the distribution of marine life. Contrasting distributional responses among species can alter the spatial overlap between predators and prey, potentially disrupting trophic interactions and affecting food web dynamics. Here, we evaluate long‐term changes in the spatial overlap of habitat suitability ranges for trophically related species, including crustaceans, fish, penguins, and pinnipeds across 12 Large Marine Ecosystems from the Southern Hemisphere, merged into three primary regions: South America, Southern Africa, Australia and New Zealand. To this aim, we first use Boosted Regression Trees (BRTs) to hindcast and project species‐specific changes in suitable habitat from 1850 to 2100 under two future climate scenarios: SSP1‐2.6 (low climate forcing) and SSP5‐8.5 (high climate forcing). We then analyze changes in species habitat suitability and potential predator–prey spatial overlaps. Findings reveal that marine species generally exhibit changes in their suitable habitats, with pronounced shifts towards higher latitudes under the SSP5‐8.5 scenario. However, contrasting trends emerge among predators across functional groups and regions of South America, Southern Africa, Australia and New Zealand. These variations highlight the need for species and regional‐specific management responses. We also project contrasting spatial mismatches between predators and prey: predators experiencing declines in suitable habitat tend to exhibit greater overlap with their prey in future scenarios, whereas those with expanding suitable habitat show reduced spatial overlap with their prey. This study provides valuable insights that can inform spatial management strategies in response to climate change and illustrate how climate change may weaken species' ability to adapt to climate‐driven environmental changes due to trophic disruptions.

Manufacturing and decorating cardial pottery: shell tools at the Neolithic site of Cabecicos Negros (Vera, Almeria, Spain) - Elena Lastra-Alonso; David Cuenca-Solana; Asier García-Escárzaga; Javier Rodríguez-Santos; Xavier Clop-García; María Dolores Camalich-Massieu; Dimas Martín-Socas (Archaeological and Anthropological Sciences, 2025)
Traditional research approaches on pottery production based on typological and morphometric classifications have changed in favour of new lines of research. One of them is based on the study of the technological equipment used in ceramic manufacturing processes. For example, ethnographic evidence shows the use of shell tools as technological equipment in different phases of ceramic production. In this study, the methodology of use-wear analysis has been applied to the archaeomalacological material from the Neolithic site of Cabecicos Negros (Andalusia, Spain) to establish if the shells were used as work tools. This analysis has been completed with the development of an experimental program composed of two analytical and one prospective experiments, carried out to provide new data about the cardial decorative technique and to define the use-wear traces that appear on the active area of the shells after their technological use. The results obtained in this investigation show the use of shells in different stages of pottery production. On the one hand, during the modelling and regularization phase of the ceramic surface and, on the other hand, during the cardial decorative phase. In this way, through this work, it has been possible to establish that the archaeological site of Cabecicos Negros was a pottery production center where domestic pieces were made during its Neolithic occupation. In addition, these findings reaffirm the importance of shells in ceramic manufacture during the Neolithic period, mainly in terms of the technical process linked to the cardial-type of ceramic decoration.

Spatiotemporal analysis of wildfires and their relationship with climate and land use in the Gran Chaco and Pantanal ecoregions - Cristina Vidal-Riveros; Bryce Currey; David B. McWethy; Marie Ange Ngo Bieng; Pablo Souza-Alonso (Science of The Total Environment, 2024)

Exploring structural and computational contrasts in Myoglobins: Implications for thermal treatment-induced Sulfmyoglobin formation - Juan C. Ramírez-Suárez; Andrés Álvarez-Armenta; Jose Angel Huerta-Ocampo; Alonso A. López-Zavala; David O. Corona-Martínez; Rogerio R. Sotelo-Mundo; Ramón Pacheco-Aguilar (Food Chemistry, 2024)

Pavlovian‐Type Learning in Environmental Bacteria: Regulation of Herbicide Resistance by Arsenic in Pseudomonas putida - David Paez‐Espino; Gonzalo Durante‐Rodríguez; Elena Alonso Fernandes; Manuel Carmona; Victor de Lorenzo (Environmental Microbiology, 2024)
The canonical arsRBC genes of the ars1 operon in Pseudomonas putida KT2440, which confer tolerance to arsenate and arsenite, are followed by a series of additional ORFs culminating in phoN1 . The phoN1 gene encodes an acetyltransferase that imparts resistance to the glutamine synthetase inhibitor herbicide phosphinothricin (PPT). The co‐expression of phoN1 and ars genes in response to environmental arsenic, along with the physiological effects, was analysed through transcriptomics of cells exposed to the oxyanion and phenotypic characterization of P. putida strains deficient in different components of the bifan motif governing arsenic resistance in this bacterium. Genetic separation of arsRBC and phoN1 revealed that their associated phenotypes operate independently, indicating that their natural co‐regulation is not functionally required for simultaneous response to the same signal. The data suggest a scenario of associative evolution, akin to Pavlovian conditioning, where two unrelated but frequently co‐occurring signals result in one regulating the other's response – even if there is no functional link between the signal and the response. Such surrogate regulatory events may provide an efficient solution to complex regulatory challenges and serve as a genetic patch to address transient gaps in evolving regulatory networks.

Selective Pressure Influences Inter‐Biome Dispersal in the Assembly of Saline Microbial Communities - Mateu Menéndez‐Serra; Joan Cáliz; Xavier Triadó‐Margarit; David Alonso; Emilio O. Casamayor (Environmental Microbiology, 2024)
Selection and dispersal are the primary processes influencing community assembly at both global and regional scales. Although the effectiveness of dispersal is often examined within the same biome, microscopic organisms demonstrate the capability to colonise and thrive across different biomes. In this study, we evaluated the relationship between (i) aquatic, (ii) sedimentary and (iii) aerial microbial communities, and how local selective pressures influence the potential impact of inter‐biome dispersal, focusing on the salinity gradient stress over time in ephemeral saline lakes. Our taxonomic ordination analyses revealed that the three communities were distinctly segregated yet interconnected by shared populations. Organisms prevalent across the three biomes exhibited cosmopolitan behaviour based on global databases, indicating an inherent ability to cross biome boundaries. Cosmopolitan groups dominated the planktonic community at lower salinities but gradually diminished as salinity increased, resulting in communities dominated by aquatic specialists with more restricted environmental distributions. The aerial community was primarily composed of generalists, although airborne halophiles were also identified, suggesting long‐range dispersal as a source of colonisers in isolated extremophile environments. Our findings contribute to a better understanding of the dynamic interplay between dispersal and selective pressures on community assembly across biomes, highlighting the significance of aerial microbiota in remote colonisation.

Longitudinal survey of hepatitis E virus in extensively raised pigs in Spain - Tomás Fajardo-Alonso; Ignacio García-Bocanegra; María A. Risalde; Antonio Rivero-Juárez; Saúl Jiménez-Ruiz; David Cano-Terriza; María Casares-Jiménez; Eduardo Laguna; Pelayo Acevedo; Mario Frías; Joaquín Vicente; Antonio Rivero; et al. (Veterinary Microbiology, 2024)

Argentina's rejection of 2030 agenda undermines environmental sustainability and human well-being - Javier Nori; Alejandro E.J. Valenzuela; Micaela Camino; Elena Abraham; Gabriela Agostini; Marcelo A. Aizen; Virginia Alonso-Roldán; Julieta R. Arcamone; Yanina Arzamendia; German Baldi; Diego Baldo; Matías C. Baranzelli; et al. (Biological Conservation, 2024)

Molecular study of the transcription factor SKN-1 and its putative relationship with genes that encode GST and antioxidant enzymes in Haemonchus contortus - Jocelyn Maza-Lopez; Verónica Jiménez-Jacinto; Víctor H. Bermúdez-Morales; Rogelio A. Alonso-Morales; David E. Reyes-Guerrero; Rosa I. Higuera-Piedrahita; Rene Camas-Pereyra; Maria Eugenia López-Arellano (Veterinary Parasitology, 2024)

Fish and tips: Historical and projected changes in commercial fish species' habitat suitability in the Southern Hemisphere - Maria Bas; Jazel Ouled-Cheikh; Laura Julià; Alba Fuster-Alonso; David March; Francisco Ramírez; Luis Cardona; Marta Coll (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Synthesis of dihydrocarvone over dendritic ZSM-5 Zeolite: A comprehensive study of experimental, kinetics, and computational insights - Luis A. Gallego-Villada; Wander Y. Perez-Sena; Julián E. Sánchez-Velandia; Jennifer Cueto; María del Mar Alonso-Doncel; Johan Wärmå; Päivi Mäki-Arvela; Edwin A. Alarcón; David P. Serrano; Dmitry Yu. Murzin (Chemical Engineering Journal, 2024)

Periorbital necrotizing fasciitis: clinical perspectives on nine cases - David Oliver-Gutierrez; R. L. P. van der Veen; Elena Ros-Sánchez; Gloria Segura-Duch; Tirso Alonso; Alejandra Herranz-Cabarcos; Jessica Matas; Roberto Castro Seco; Miguel Ángel Arcediano; Miguel Ángel Zapata; Joan Oliveres (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

In-situ observations of resident space objects with the CHEOPS space telescope - Nicolas Billot; Stephan Hellmich; Willy Benz; Andrea Fortier; David Ehrenreich; Christopher Broeg; Alexis Heitzmann; Anja Bekkelien; Alexis Brandeker; Yann Alibert; Roi Alonso; Tamas Bárczy; et al. (Journal of Space Safety Engineering, 2024)

Deciphering the plot preferences of forest contractors when purchasing stumpage through conjoint analysis - Laura Alonso; Juan Picos; Maria del Carmen Iglesias-Pérez; David Iglesias-González; Julia Armesto (Forest Policy and Economics, 2024)

Analysis of cell growth, photosynthetic behavior and the fatty acid profile in Tetraselmis subcordiformis under different lighting scenarios - Laura María Montoya Montoya; Andrés Alonso Arbeláez Pérez; Néstor David Giraldo Calderón; Lucía Atehortúa Garcés (Journal of Applied Phycology, 2024)
Tetraselmis has been investigated as a potential source of lipids. This microalga possesses good growth characteristics and can be used to develop viable platforms for fatty acid production. This research aims to evaluate the effect of high photon flux density with light-dark cycles and light wavelength on biomass production and fatty acid profile in Tetraselmis subcordiformis. A low light control and treatments with high photon flux density with different light-dark cycles (24:0 h, 12:12 h, 1:1 h, and 15:15 min) and different light wavelength (white, green, red, and blue) were evaluated to determine cell concentration, nutrient consumption, chlorophyll content, photosynthetic yields, lipid content, and fatty acid profile. Significant differences were found in all variables, except for phosphate consumption. High photon flux density promotes cell growth with T. subcordiformis reaching biomass productivities of 0.10 g L -1 day -1 when continuous white light is used. However, no differences were observed in biomass productivities and lipid content for all high photon flux density treatments. On the other hand, red light resulted in higher cell growth, with a productivity of 0.12 g L -1 day -1 , and the highest lipid content was achieved under white light. There was a significant effect on the fatty acid profile under different light conditions, with palmitic acid, oleic acid, and eicosapentaenoic acid being the most abundant. This study demonstrated that cellular growth and fatty acid profiles in T. subcordiformis can be influenced by different lighting schemes in the cultivation.

Nanoemulsions and nanocapsules as carriers for the development of intranasal mRNA vaccines - Mireya L. Borrajo; Gustavo Lou; Shubaash Anthiya; Philipp Lapuhs; David Moreira Álvarez; Araceli Tobío; María Isabel Loza; Anxo Vidal; María José Alonso (Drug Delivery and Translational Research, 2024)
The global emergency of coronavirus disease 2019 (COVID-19) has spurred extensive worldwide efforts to develop vaccines for protection against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Our contribution to this global endeavor involved the development of a diverse library of nanocarriers, as alternatives to lipid nanoparticles (LNPs), including nanoemulsions (NEs) and nanocapsules (NCs), with the aim of protecting and delivering messenger ribonucleic acid (mRNA) for nasal vaccination purposes. A wide range of prototypes underwent rigorous screening through a series of in vitro and in vivo experiments, encompassing assessments of cellular transfection, cytotoxicity, and intramuscular administration of a model mRNA for protein translation. As a result, two promising candidates were identified for nasal administration. One of them was a NE incorporating a combination of an ionizable lipid (C12-200) and cationic lipid (DOTAP), both intended to condense mRNA, along with DOPE, which is known to facilitate endosomal escape. This NE exhibited a size of 120 nm and a highly positive surface charge (+ 50 mV). Another candidate was an NC formulation comprising the same components and endowed with a dextran sulfate shell. This formulation showed a size of 130 nm and a moderate negative surface charge (-16 mV). Upon intranasal administration of mRNA encoding for ovalbumin (mOVA) associated with optimized versions of the said NE and NCs, a robust antigen-specific CD8 + T cell response was observed. These findings underscore the potential of NEs and polymeric NCs in advancing mRNA vaccine development for combating infectious diseases. Graphical Abstract

Photosynthetic distribution inside a cylindrical photobioreactor for Botryococcus braunii: A fed-batch culture application - Andrés Alonso Arbeláez Pérez; Néstor David Giraldo Calderón; Laura María Montoya Montoya; Lucía Atehortúa Garcés (Algal Research, 2024)

Impact of ocean in-situ observations on ECMWF sub-seasonal forecasts - Beena Balan-Sarojini; Magdalena Alonso Balmaseda; Frédéric Vitart; Christopher David Roberts; Hao Zuo; Steffen Tietsche; Michael Mayer (Frontiers in Marine Science, 2024)
We assess for the first time the impact of in-situ ocean observations on European Centre for Medium-Range Weather Forecasts (ECMWF) sub-seasonal forecasts of both ocean and atmospheric conditions. A series of coupled reforecasts have been conducted for the period 1993-2015, in which different sets of ocean observations were withdrawn in the production of the ocean initial conditions. Removal of all ocean in-situ observations in the initial conditions leads to significant degradation in the forecasts of ocean surface and subsurface mean state at lead times from week 1 to week 4. The negative impact is predominantly caused by the removal of the Argo observing system in recent decades. Changes in the mean state of atmospheric variables are comparatively small but significant in the forecasts of lower and upper atmospheric circulation over large regions. Our results highlight the value of continuous, real-time in-situ observations of the surface and subsurface ocean for coupled forecasts in the sub-seasonal range.

Validation and parametrization of the soil moisture index for stomatal conductance modelling and flux-based ozone risk assessment of Mediterranean plant species - Tania Carrasco-Molina; Riccardo Marzuoli; Vicent Calatayud; David Simpson; Giacomo Gerosa; Arnaud Carrara; Isaura Rábago; Rocío Alonso; Ignacio González-Fernández (Agricultural and Forest Meteorology, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Bloodstream infections: trends and evolution of incidence and etiology in a 12-year period (2010–2021) - David Alonso-Menchén; Carlos Sánchez-Carrillo; Luis Alcalá; Ana Soriano-Martín; Emilia Cercenado; Almudena Burillo; Julia Serrano-Lobo; Leire Pérez-Latorre; Patricia Muñoz; Emilio Bouza (Infectious Diseases, 2024)

Reassessing science communication for effective farmland biodiversity conservation - Elena Velado-Alonso; David Kleijn; Ignasi Bartomeus (Trends in Ecology & Evolution, 2024)

End-over-end (EoE) rotation of toroidal cans: An experimentally validated mathematical modelling study - David Alonso de Mezquia; Uxue Arrieta; M. Mounir Bou-Ali; Ozan Altin; Eda Coskun; Trond Løvdal; Dagbjørn Skipnes; Bart Van Droogenbroeck; Fabrizio Sarghini; Ferruh Erdogdu (Innovative Food Science & Emerging Technologies, 2024)

Integrated coastal zone management in Colombia: 25 years of implementing an environmental planning policy - Paula Cristina Sierra-Correa; Ángela Cecilia López Rodríguez; David Alejandro Alonso Carvajal; Francisco Armando Arias Isaza (Marine Policy, 2024)

Source identification from unperceived low-frequency noise emissions at a Madrid home - León José Azcárate de Castro; David Baeza-Moyano; Gastón Sanglier Contreras; Roberto Alonso González-Lezcano (Building and Environment, 2024)

Tracking data highlight the importance of human-induced mortality for large migratory birds at a flyway scale - Juan Serratosa; Steffen Oppel; Shay Rotics; Andrea Santangeli; Stuart H.M. Butchart; Luis S. Cano-Alonso; Jose Luis Tellería; Ryno Kemp; Aaron Nicholas; Aigars Kalvāns; Aitor Galarza; Aldina M.A. Franco; et al. (Biological Conservation, 2024)

PRIMASS near-infrared study of the Erigone collisional family - Brittany Harvison; Mário De Prá; Noemí Pinilla-Alonso; Vania Lorenzi; Julia de León; David Morate; Javier Licandro; Anicia Arredondo; Humberto Campins (Icarus, 2024)

Moult performance varies in relation to colour patterns in crossbills - Blanca Fernández-Eslava; Daniel Alonso; David Galicia; Juan Arizaga (Journal of Ornithology, 2024)
Carotenoid-based ornamentation can vary greatly among individual birds of the same population. This variability might consider the timing and duration of moult. Crossbills (genus Loxia ) show large variation in their colour patterns, ranging from dull yellow to red. Thus, they provide an excellent avian model for testing whether the timing and duration of their moult are associated with their dominant colour patterns. Using a dataset of more than 1900 crossbills captured in the Pyrenees (Spain), we observed that individuals with red feathers started their primary moult early, while those with yellow feathers started moult on an average of 18 days later. We also found that yellow crossbills were more likely to suspend moults (i.e. temporally interrupt moult), postponing a part of the moult until September. These differences in the moulting process may be related to plumage colour, which reflect individual condition.

Chemical and C and N stable isotope compositions of three species of epiphytic Tillandsia in a Caribbean coastal zone: air pollution sources and biomonitoring implications - Yasser Morera-Gómez; Alejandro Armas-Camejo; Jesús Miguel Santamaría; Carlos Manuel Alonso-Hernández; Esther Lasheras; David Widory; David Elustondo (Isotopes in Environmental and Health Studies, 2024)

Is the Chinese crude oil spot price a good hedging tool for other crude oil prices, and in special for the main Russian oil benchmarks and during international sanctions? - David Rivera-Alonso; Emma M. Iglesias (Resources Policy, 2024)

Effects of feeding with a protein liquid supplement on productivity, mortality and health of Apis mellifera hives in southwestern Spain - Eduardo José García-Vicente; María Martín; Ismael Rey-Casero; Ana Pérez; Jairo Martín; Alfredo García; Juan Manuel Alonso; David Risco (Research in Veterinary Science, 2024)

Revisiting the mercury cycle in marine sediments: A potential multifaceted role for Desulfobacterota - Blanca Rincón-Tomás; Anders Lanzén; Pablo Sánchez; Mónica Estupiñán; Isabel Sanz-Sáez; M. Elisabete Bilbao; Diana Rojo; Iñaki Mendibil; Carla Pérez-Cruz; Marta Ferri; Eric Capo; Ion L. Abad-Recio; et al. (Journal of Hazardous Materials, 2024)

The role of automatic pollen and fungal spore monitoring across major end-user domains - Fiona Tummon; Beverley Adams-Groom; Célia M. Antunes; Nicolas Bruffaerts; Jeroen Buters; Paloma Cariñanos; Sevcan Celenk; Marie Choël; Bernard Clot; Antonella Cristofori; Benoît Crouzy; Athanasios Damialis; et al. (Aerobiologia, 2024)
The advent of automatic pollen and fungal spore monitoring over the past few years has brought about a paradigm change. The provision of real-time information at high temporal resolution opens the door to a wide range of improvements in terms of the products and services made available to a widening range of end-users and stakeholders. As technology and methods mature, it is essential to properly quantify the impact automatic monitoring has on the different end-user domains to better understand the real long-term benefits to society. In this paper, we focus the main domains where such impacts are expected, using Europe as a basis to provide qualitative estimates and to describe research needs to better quantify impacts in future. This will, in part, also serve to justify further investment and help to expand monitoring networks.

Applying a water-energy-food nexus approach to seafood products from the European Atlantic area - Sandra Ceballos-Santos; Eduardo Entrena-Barbero; Jara Laso; María Margallo; Sara González-García; María Teresa Moreira; Cheila Almeida; António Marques; Paula Quinteiro; Ana Cláudia Dias; Pedro Villanueva-Rey; Philippe Loubet; et al. (Journal of Cleaner Production, 2024)

Enhanced oil dehalogenation during catalytic pyrolysis of WEEE-derived plastics over Fe- and Ca-modified zeolites - Julio López; Lidia Amodio; Maria del Mar Alonso-Doncel; Jennifer Cueto; Hector Hernando; Michal Mazur; Jiří Čejka; Patricia Pizarro; David P. Serrano (Journal of Environmental Chemical Engineering, 2024)

Description of new species of Trematoda from bats of Southeastern Mexico and a new classification for Brachylecithum rileyi n. comb. (Dicrocoeliidae) - Wilson I. Moguel-Chin; Jesús Alonso Panti-May; Brenda Atziri García-García; David I. Hernández-Mena (Systematic Parasitology, 2024)
To date, 23 species of trematodes have been reported in bats from Mexico. However, in some regions of Mexico, such as the Yucatan Peninsula, many species of bats do not have helminthological records. Here, we sampled bats in four localities in Southeastern Mexico from April 2017 to February 2022. Parasites were collected from the intestine of four species of bats: Pteronotus fulvus , Eumops nanus , Noctilio leporinus and Nyctinomops laticaudatus . Conventional morphological techniques and molecular tools with the 28S ribosomal gene were used to describe the helminths. We discovered that our parasites represent three new species and a new combination of trematodes. We found that the new species have morphological differences with their congeneric species, and we complement this information whit molecular data. Furthermore, we found morphological and molecular evidence that places Dicrocoelium rileyi within the genus Brachylecithum . This study points out the importance of comparing morphological and phylogenetic information.

Does sustainability improve financial performance? An analysis of Latin American oil and gas firms - Javier Rojo-Suárez; Ana B. Alonso-Conde; Juan David Gonzalez-Ruiz (Resources Policy, 2024)

A nationwide monitoring of atmospheric microplastic deposition - Carlos Edo; Francisca Fernández-Piñas; Francisco Leganes; May Gómez; Ico Martínez; Alicia Herrera; Cintia Hernández-Sánchez; Javier González-Sálamo; Javier Hernández Borges; Joaquín López-Castellanos; Javier Bayo; Cristina Romera-Castillo; et al. (Science of The Total Environment, 2023)

Contourite stratigraphic models linked to the light intermediate versus dense deep Mediterranean water flow regime variations (Alboran Sea, SW Mediterranean) - Belén Alonso; Gemma Ercilla; Carmen Juan; Nieves López-González; Isabel Cacho; Guillermo Francés; Desirée Palomino; Patricia Bárcenas; Mariano Yenes; José Nespereira; Blanca Ausín; Pilar Mata; et al. (Marine Geology, 2023)

Natural radionuclides behaviour in drinking groundwaters from Castilla y León (Spain); radiological implications - David Borrego-Alonso; Begoña Quintana-Arnés; Juan Carlos Lozano (Water Research, 2023)

Binaural Beat Effects on Attention: A Study Based on the Oddball Paradigm - Luis Kevin Cepeda-Zapata; César E. Corona-González; Luz María Alonso-Valerdi; David I. Ibarra-Zarate (Brain Topography, 2023)

The EnMAP imaging spectroscopy mission towards operations - Tobias Storch; Hans-Peter Honold; Sabine Chabrillat; Martin Habermeyer; Paul Tucker; Maximilian Brell; Andreas Ohndorf; Katrin Wirth; Matthias Betz; Michael Kuchler; Helmut Mühle; Emiliano Carmona; et al. (Remote Sensing of Environment, 2023)

Trends of legacy and emerging organic contaminants in a sediment core from Cienfuegos Bay, Cuba, from 1990 to 2015 - Brigid Carr; Pere Masqué; Carlos M. Alonso-Hernández; David Huertas; Philippe Bersuder; Imma Tolosa (Chemosphere, 2023)

Involvement of the excretory/secretory and surface-associated antigens of Dirofilaria immitis adult worms in the angiogenic response in an in-vitro endothelial cell model - Cristian David Cardona Machado; Claudia Alarcón-Torrecillas; Miguel Pericacho; Iván Rodríguez-Escolar; Elena Carretón; José Alberto Montoya-Alonso; Rodrigo Morchón (Veterinary Parasitology, 2023)

Effect of feed supplementation with probiotics and postbiotics on strength and health status of honey bee (Apis mellifera) hives during late spring - Eduardo José García-Vicente; María Martín; Ismael Rey-Casero; Ana Pérez; Remigio Martínez; María Bravo; Juan Manuel Alonso; David Risco (Research in Veterinary Science, 2023)

Sulfmyoglobin production by free cysteine during thermal treatment: Involvement of heme iron in the production of free radicals - Andrés Álvarez-Armenta; David O. Corona-Martínez; Ramón Pacheco-Aguilar; Alonso A. López-Zavala; Rogerio R. Sotelo-Mundo; Guillermina García-Sánchez; Juan Carlos Ramírez-Suárez (Food Chemistry, 2023)

Seasonal Upwelling Conditions Modulate the Calcification Response of a Tropical Scleractinian Coral - Carlos Gómez; Andrés Acosta-Chaparro; Cesar Bernal; Diana Gómez-López; Raúl Navas-Camacho; David Alonso (Oceans, 2023)
Natural processes such as upwelling of deeper-water masses change the physical-chemical conditions of the water column creating localized ocean acidification events that can have an impact on the natural communities. This study was performed in a coral reef system of an archetypical bay within the Tayrona National Natural Park (PNNT) (Colombia), and aimed to quantify net calcification rates of a foundational coral species within a temporal context (6 months) taking into account the dynamics of seasonal upwelling that influence the study area. Net calcification rates of coral fragments were obtained in situ by the alkalinity anomaly technique in short-term incubations (~2.5 h). We found a significant effect of the upwelling on net calcification rates (Gnet) (p < 0.05) with an 42% increase in CaCO3 accretion compared to non-upwelling season. We found an increase in total alkalinity (AT) and dissolved inorganic carbon (DIC) with decreased aragonite saturation (Ωara) for the upwelling months, indicating an influence of the Subtropical Under Water mass (SAW) in the PNNT coral community. Significant negative correlations between net calcification with temperature and Ωara, which indicates a positive response of M. auretenra with the upwelling conditions, thus, acting as “enhancer” of resilience for coral calcification.

Planktonic foraminifera response to orbital and millennial-scale climate variability at the southern Iberian Margin (IODP Site U1385) during Marine Isotope Stages 20 and 19 - Angela Girone; Adriano De Astis; Francisco J. Sierro; Ivan Hernández-Almeida; Montserrat Alonso Garcia; Maria F. Sánchez Goñi; Patrizia Maiorano; Maria Marino; Samanta Trotta; David Hodell (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Understanding stochastic and deterministic assembly processes in microbial communities along temporal, spatial and environmental scales - Mateu Menéndez‐Serra; Vicente J. Ontiveros; Joan Cáliz; David Alonso; Emilio O. Casamayor (Molecular Ecology, 2023)
Identifying the main drivers of community assembly remains an open fundamental question in ecology. Dispersal processes introduce randomness in community composition while selection for particular environments creates predictable assemblages. However, the interaction between selection and dispersal processes is still poorly understood. Here, we address this question in bacterial and microeukaryotic communities inhabiting a highly dynamic system of ephemeral (hyper)saline lakes. We show that the combination of beta‐diversity decomposition methods and a temporal approach based on colonization and extinction dynamics yields new insights into the relative effect of selection and dispersal along environmental gradients. Selective pressure and dispersal‐related processes simultaneously shape each local community with variable strength and effect. The dominance of selection vs. dispersal shifted from stochastic to deterministic assembly as salinity increased along the gradient. This transition also had an impact on the temporal dynamics of the lakes as community turnover decreased at high salinities because both colonization and extinction rates slowed down. Only microeukaryotic richness decreased along the gradient due to lower effective colonization at higher salinities, suggesting that the net effect of selection and dispersal is determined by both environmental conditions and the idiosyncrasy of the different microbial ecologies. Our results emphasize the use of temporal approaches in combination with standard statistical methods for a better understanding of the dynamic processes underlying community assembly.

Towards European automatic bioaerosol monitoring: Comparison of 9 automatic pollen observational instruments with classic Hirst-type traps - José M. Maya-Manzano; Fiona Tummon; Reto Abt; Nathan Allan; Landon Bunderson; Bernard Clot; Benoît Crouzy; Gintautas Daunys; Sophie Erb; Mónica Gonzalez-Alonso; Elias Graf; Łukasz Grewling; et al. (Science of The Total Environment, 2023)

Sensitivity of solar-induced fluorescence to spectral stray light in high resolution imaging spectroscopy - Loren P. Albert; K.C. Cushman; Yuqin Zong; David W. Allen; Luis Alonso; James R. Kellner (Remote Sensing of Environment, 2023)

Mapping first to final uses for rare earth elements, globally and in the United States - Elisa Alonso; David G. Pineault; Joseph Gambogi; Nedal T. Nassar (Journal of Industrial Ecology, 2023)
Estimating the material flows of rare earth elements (REEs) is essential to understanding which industries are most vulnerable to potential REE supply disruptions which, in turn, may inform policy recommendations aimed at reducing the supply risk. However, the REEs are a group of mineral commodities characterized by highly uncertain estimates of supply and demand due to the REE market's complexity, opacity, and small size. In this study, a streamlined methodology was applied to map mineral commodity first‐use to final‐use applications and to estimate total requirements at the national level based on available industrial data for final‐use finished goods. This analysis examines REEs both as a group and individually, showing that total US requirements are between 15% and 16.5% of world requirements for the year 2015, the latest year with the most complete information available. The findings shed light on US industrial capabilities by revealing the discrepancy between the types of REEs that go into US raw material consumption and those that are contained in embedded consumption. For instance, given the United States’ large oil refining industry, US raw material consumption of lanthanum is quite high. In contrast, US raw material consumption of neodymium is relatively low, whereas embedded demand is comparatively high. This reflects the lack of industrial capacity to process REE concentrates into magnet material combined with the US's high imports of products that contain rare earth permanent magnets.

Streamlined approach for assessing embedded consumption of lithium and cobalt in the United States - Elisa Alonso; David Pineault; Nedal T. Nassar (Journal of Industrial Ecology, 2023)
In today's complex global supply chains, time and data intensive analyses are required to understand global flows of mineral commodities from mine to consumer, particularly for mineral commodities in products (electronics, automobiles, etc.) that contain multiple parts with many mineral commodities. National and regional analyses require additional time and data to incorporate international trade flows. However, data limitations and time constraints often prohibit global and national material flow analyses for minor metals. Here we present a methodological approach to circumvent these constraints by utilizing readily available industry‐level global data from the United Nations Statistics Division and national industrial data to estimate total requirements for a mineral commodity. We apply this approach to lithium and cobalt use in the United States for the year 2018 and distinguish between apparent raw material consumption versus inferred embedded consumption of lithium and cobalt materials in all forms. The results show that more than half of the United States’ total requirements for both lithium and cobalt is in parts and products that were manufactured outside the United States. In large part, this is due to limited US manufacturing capability for lithium‐ion battery materials and cells and the United States’ high import reliance for electronics that use those batteries.

Mitochondria and light: An overview of the pathways triggered in skin and retina with incident infrared radiation - Daniel Arranz-Paraíso; Yolanda Sola; David Baeza-Moyano; Marta Benítez-Martínez; Sofía Melero-Tur; Roberto Alonso González-Lezcano (Journal of Photochemistry and Photobiology B: Biology, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

250-Year reconstruction of pollarding events reveals sharp management changes in Iberian ash woodlands - David Candel-Pérez; Héctor Hernández-Alonso; Federico Castro; Gabriel Sangüesa-Barreda; Sven Mutke; Miguel García-Hidalgo; Vicente Rozas; José Miguel Olano (Trees, 2022)
Key message Tree-ring growth of pollarded narrow-leaved ash trees in Central Spain reveals traditional management cessation in 1970 and property-specific management patterns. Abstract Tree pollarding was a dominant management strategy of European forests for centuries creating open agroforestry landscapes with important cultural and environmental values. This traditional practice has been widely abandoned in last decades with a subsequent impact in terms of biodiversity and cultural loss. Central Spain hosts the largest and best-preserved area of pollarded narrow-leaved ash ( Fraxinus angustifolia Vahl.) woodlands in Europe. The main aim of this research is to obtain rigorous historical records of pollarding frequency to get adequate information for traditional ash management. We used dendrochronological techniques to evaluate temporal changes of pollarding frequency and rotation length. We analysed the stand level synchrony and the effect of land property on pollarding activity from 322 trees growing in eight pollard stands in Central Spain. Pollarding events were unequivocally identified at tree level by a characteristic change in growth pattern. We identified 2426 tree-level pruning events with the first event dated in 1777. Historical pruning recurrence ranged between 5 and 10 years with higher pollarding frequency on private lands. Pruning events within each site were synchronous, suggesting the existence of a rotational schema within each stand. Pruning frequency decreased drastically in the 1970s matching with the depopulation of rural areas and the general abandonment of traditional practices. Pollarding practices have recovered in recent decades although with lower intensity and lacking the synchronic historical patterns. Providing technical and economic support to make this traditional activity profitably would have strong environmental revenue due the multiple ecosystem services provided by pollarded ashes.

A comprehensive threat analysis to support the red list of marine and coastal ecosystems of Colombia - Edwin S. Uribe; Andrés Etter; Andrea Luna-Acosta; María Claudia Diazgranados; David Alonso; Luis Chasqui; Adriana Osorno; Alberto Acosta; Alexandra Rodríguez-Rodríguez; Constanza Ricaurte-Villota; Luisa Escobar; Alan Giraldo (Frontiers in Marine Science, 2022)
Introduction Human activities represent a growing threat to biodiversity, increasing species extinction and leading ecosystems to collapse. The knowledge of the spatial distribution of threats to ecosystems is fundamental to understanding their risk of collapse as defined by the Red List of Ecosystems, an International Union for Conservation of Nature (IUCN) global standard to guide conservation and management actions. Colombia is a megadiverse country; almost half of its territory is marine, and its ecosystems are subject to anthropogenic and climatic threats. Methodology This study provides a quantitative map assessment for a set of relevant anthropic and climatic threats and impacts on the marine and coastal areas of Colombia, intending to perform the threat description component of the Red List assessment protocol. A cumulative impact assessment was applied to analyze the threat levels (TLs) and impact levels of 12 anthropogenic and climatic pressures. Results The observed TL patterns meet spatial expectations, revealing that the assessment units in the Caribbean Sea are more threatened than those in the Pacific Ocean, and continental areas are more threatened than the oceanic ones. Habitat transformation and sea warming were the threats with the most impact on coastal and marine ecosystems, respectively. Climatic threats were widely extended throughout the study area, occurring even in the most pristine zones (e.g., Malpelo Island). Discussion Climate threats are challenging to national conservation strategies since these pressures are not completely manageable at local scales as they depend mainly on global efforts. Recommendations drawn from this work can guide actions for the conservation of the ecosystems of Colombia.

Benthic macrohabitat classification and Madracis spp. coral patch distribution in a deep-sea marine protected area of Colombia - Cristina Cedeño-Posso; Martha Vides-Casado; Venus Rocha; Giomar H. Borrero-Pérez; Andrea Polanco F; David Alonso (Frontiers in Marine Science, 2022)
Corales de Profundidad National Natural Park (CPNNP), at the central Colombian Caribbean margin, has an extension of 142.195 ha with depths ranging from 34 to 1,234 m. The CPNNP’s essential ecological value is Madracis spp. as potential structure-forming deep-water coral; this work represents the first footages of these unique habitats for the Colombian Caribbean. In 11 sectors, remote video surveys are conducted, based on a detailed digital elevation model. From these sectors, four cover mesophotic zones (46–169m depth), and seven cover aphotic zones (up to 354m depth). After still images’ description and interpretation, a guide was generated with nine types of macrohabitats surrounding the coral formations of the CPNNP: soft substrate (mud/sand), soft substrate/rubble/rock with solitary corals, coral and shell rubble, rock/ledges with attached fauna, rugged stones with attached fauna, hard substrate with attached fauna, sandstone with attached fauna, soft substrate with burrows, and pockmark with attached fauna. Video transect analysis confirms the occurrence of Madracis spp., with coral patches as the main framework builder of the CPNNP. These patches comprise many clumped 50 to 80 cm high coral colonies that developed over slow slopes, with seafloor elevations between 107 and 233 m and textured soils of soft and not very compact ridges, associated with the macrohabitat sandstone with attached fauna. This information is being used for the management and monitoring of this unique protected area.

Bone diagenesis in dry tropic forest necrosols - Timisay Monsalve-Vargas; David Arboleda; Santiago Vélez; Santiago-Alonso Cardona-Gallo (Archaeological and Anthropological Sciences, 2022)

Toward a decade of ocean science for sustainable development through acoustic animal tracking - Josep Alós; Kim Aarestrup; David Abecasis; Pedro Afonso; Alexandre Alonso‐Fernandez; Eneko Aspillaga; Margarida Barcelo‐Serra; Jonathan Bolland; Miguel Cabanellas‐Reboredo; Robert Lennox; Ross McGill; Aytaç Özgül; et al. (Global Change Biology, 2022)
The ocean is a key component of the Earth's dynamics, providing a great variety of ecosystem services to humans. Yet, human activities are globally changing its structure and major components, including marine biodiversity. In this context, the United Nations has proclaimed a Decade of Ocean Science for Sustainable Development to tackle the scientific challenges necessary for a sustainable use of the ocean by means of the Sustainable Development Goal 14 (SDG14). Here, we review how Acoustic animal Tracking, a widely distributed methodology of tracking marine biodiversity with electronic devices, can provide a roadmap for implementing the major Actions to achieve the SDG14. We show that acoustic tracking can be used to reduce and monitor the effects of marine pollution including noise, light, and plastic pollution. Acoustic tracking can be effectively used to monitor the responses of marine biodiversity to human‐made infrastructures and habitat restoration, as well as to determine the effects of hypoxia, ocean warming, and acidification. Acoustic tracking has been historically used to inform fisheries management, the design of marine protected areas, and the detection of essential habitats, rendering this technique particularly attractive to achieve the sustainable fishing and spatial protection target goals of the SDG14. Finally, acoustic tracking can contribute to end illegal, unreported, and unregulated fishing by providing tools to monitor marine biodiversity against poachers and promote the development of Small Islands Developing States and developing countries. To fully benefit from acoustic tracking supporting the SDG14 Targets, trans‐boundary collaborative efforts through tracking networks are required to promote ocean information sharing and ocean literacy. We therefore propose acoustic tracking and tracking networks as relevant contributors to tackle the scientific challenges that are necessary for a sustainable use of the ocean promoted by the United Nations.

Strategic roadmap to assess forest vulnerability under air pollution and climate change - Alessandra De Marco; Pierre Sicard; Zhaozhong Feng; Evgenios Agathokleous; Rocio Alonso; Valda Araminiene; Algirdas Augustatis; Ovidiu Badea; James C. Beasley; Cristina Branquinho; Viktor J. Bruckman; Alessio Collalti; et al. (Global Change Biology, 2022)
Although it is an integral part of global change, most of the research addressing the effects of climate change on forests have overlooked the role of environmental pollution. Similarly, most studies investigating the effects of air pollutants on forests have generally neglected the impacts of climate change. We review the current knowledge on combined air pollution and climate change effects on global forest ecosystems and identify several key research priorities as a roadmap for the future. Specifically, we recommend (1) the establishment of much denser array of monitoring sites, particularly in the South Hemisphere; (2) further integration of ground and satellite monitoring; (3) generation of flux‐based standards and critical levels taking into account the sensitivity of dominant forest tree species; (4) long‐term monitoring of N, S, P cycles and base cations deposition together at global scale; (5) intensification of experimental studies, addressing the combined effects of different abiotic factors on forests by assuring a better representation of taxonomic and functional diversity across the ~73,000 tree species on Earth; (6) more experimental focus on phenomics and genomics; (7) improved knowledge on key processes regulating the dynamics of radionuclides in forest systems; and (8) development of models integrating air pollution and climate change data from long‐term monitoring programs.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Cover Image - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)

A global agenda for advancing freshwater biodiversity research - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)
Global freshwater biodiversity is declining dramatically, and meeting the challenges of this crisis requires bold goals and the mobilisation of substantial resources. While the reasons are varied, investments in both research and conservation of freshwater biodiversity lag far behind those in the terrestrial and marine realms. Inspired by a global consultation, we identify 15 pressing priority needs, grouped into five research areas, in an effort to support informed stewardship of freshwater biodiversity. The proposed agenda aims to advance freshwater biodiversity research globally as a critical step in improving coordinated actions towards its sustainable management and conservation.

Descending necrotizing mediastinitis from Ludwig’s angina: a life-threatening condition - Miguel F. Carrascosa; Silvia Cayón Hoyo; Roberto Echeverría San-Sebastián; Iratxe Alcalde Díez; Sergio Tapia Concha; Sandra Campos Fernández; Eva María Alonso-Fernández; Carmen González-Carrero Sixto; David Lobo Duro; Laura Sánchez Moreno; Miguel Ángel Zabaleta-Murguiondo (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

Estimating the Influence of Oyster Reef Chains on Freshwater Detention at the Estuary Scale Using Landsat-8 Imagery - Alice Alonso; Natalie G. Nelson; Simeon Yurek; David Kaplan; Maitane Olabarrieta; Peter Frederick (Estuaries and Coasts, 2022)

Strong evidence supporting a relationship between colour pattern and apparent survival in common crossbills - Blanca Fernández-Eslava; Daniel Alonso; David Galicia; Juan Arizaga (Journal of Ornithology, 2022)
Carotenoid staining has been repeatedly shown to serve as a sexually selected individual quality signal. In different species, individuals that show brighter carotenoid-based signals have been found to have superior feeding abilities, recover faster from disease, and generally enjoy better body condition. In the common crossbill ( Loxia curvirostra ), the colour has also been related to the different populations, with northern and central European populations being described as redder than those in the Mediterranean region. A study in the Pyrenees showed that long-winged individuals had lower apparent survival, and the proportion of red individuals was higher in long-winged birds, concluding that they could be nomadic birds (that travel long distances). A priori, if the red crossbills are more mobile than the yellow and orange ones, their apparent survival will be lower. However, in our study, red males showed a greater survival than males of other colours and almost double than that of the yellow ones. These results suggest that red coloration is linked to higher quality individuals regardless of their mobility.

Detection of Vigil and Fatigue States During Laparoscopic Tasks Based on EEG Patterns: Towards Neuroergonomics in Medical Training - Yeremi Pérez; Roberto Borboa-Gastelum; Luz María Alonso-Valerdi; David I. Ibarra-Zárate; Eduardo A. Flores-Villalba; Ciro A. Rodríguez-González (Journal of Medical and Biological Engineering, 2021)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

The Road to the Beijing Winter Olympics and Beyond: Opinions and Perspectives on Physiology and Innovation in Winter Sport - Jun Wang; Hongwei Guan; Morten Hostrup; David S. Rowlands; José González-Alonso; Jørgen Jensen (Journal of Science in Sport and Exercise, 2021)
Beijing will host the 2022 Winter Olympics, and China strengthens research on various aspects to allow their athletes to compete successfully in winter sport. Simultaneously, Government-directed initiatives aim to increase public participation in recreational winter sport. These parallel developments allow research to advance knowledge and understanding of the physiological determinants of performance and health related to winter sport. Winter sport athletes often conduct a substantial amount of training with high volumes of low-to-moderate exercise intensity and lower volumes of high-intensity work. Moreover, much of the training occur at low ambient temperatures and winter sport athletes have high risk of developing asthma or asthma-related conditions, such as exercise-induced bronchoconstriction. The high training volumes require optimal nutrition with increased energy and dietary protein requirement to stimulate muscle protein synthesis response in the post-exercise period. Whether higher protein intake is required in the cold should be investigated. Cross-country skiing is performed mostly in Northern hemisphere with a strong cultural heritage and sporting tradition. It is expected that innovative initiatives on recruitment and training during the next few years will target to enhance performance of Chinese athletes in classical endurance-based winter sport. The innovation potential coupled with resourcing and population may be substantial with the potential for China to become a significant winter sport nation. This paper discusses the physiological aspects of endurance training and performance in winter sport highlighting areas where innovation may advance in athletic performance in cold environments. In addition, to ensure sustainable development of snow sport, a quality ski patrol and rescue system is recommended for the safety of increasing mass participation.

An integrated assessment of the impacts of PM2.5 and black carbon particles on the air quality of a large Brazilian city - Lars Gidhagen; Patricia Krecl; Admir Créso Targino; Gabriela Polezer; Ricardo H. M. Godoi; Erika Felix; Yago A. Cipoli; Isabella Charres; Francisco Malucelli; Alyson Wolf; Marcelo Alonso; David Segersson; et al. (Air Quality, Atmosphere & Health, 2021)
Data on airborne fine particle (PM 2.5 ) emissions and concentrations in cities are valuable for traffic and air quality managers, urban planners, health practitioners, researchers, and ultimately for legislators and decision makers. Emissions and ambient concentrations of PM 2.5 and black carbon (BC) were assessed in the city of Curitiba, southern Brazil. The methodology combined a month-long monitoring campaign with both fixed and mobile instruments, development of emission inventories, and dispersion model simulations on different scales. The mean urban background PM 2.5 concentrations during the campaign were 7.3 μg m −3 in Curitiba city center, but three- to fourfold higher (25.3 μg m -3 ) in a residential area on the city’s outskirts, indicating the presence of local sources, possibly linked to biomass combustion. BC concentrations seemed to be more uniformly distributed over the city, with mean urban background concentrations around 2 μg m −3 , half of which due to local traffic emissions. Higher mean BC concentrations (3–5 μg m -3 ) were found along busy roads. The dispersion modeling also showed high PM 2.5 and BC concentrations along the heavily transited ring road. However, the lack of in situ data over these peripheral areas prevented the verification of the model output. The vehicular emission factors for PM 2.5 and BC from the literature were found not to be suitable for Curitiba’s fleet and needed to be adjusted. The integrated approach of this study can be implemented in other cities, as long as an open data policy and a close cooperation among regional, municipal authorities and academia can be achieved.

Arsenic in Latin America: New findings on source, mobilization and mobility in human environments in 20 countries based on decadal research 2010-2020 - Jochen Bundschuh; Maria Aurora Armienta; Nury Morales-Simfors; Mohammad Ayaz Alam; Dina L. López; Valeria Delgado Quezada; Sebastian Dietrich; Jerusa Schneider; Joseline Tapia; Ondra Sracek; Elianna Castillo; Lue-Meru Marco Parra; et al. (Critical Reviews in Environmental Science and Technology, 2021)

Ecosystems monitoring powered by environmental genomics: A review of current strategies with an implementation roadmap - Tristan Cordier; Laura Alonso‐Sáez; Laure Apothéloz‐Perret‐Gentil; Eva Aylagas; David A. Bohan; Agnès Bouchez; Anthony Chariton; Simon Creer; Larissa Frühe; François Keck; Nigel Keeley; Olivier Laroche; et al. (Molecular Ecology, 2021)
A decade after environmental scientists integrated high‐throughput sequencing technologies in their toolbox, the genomics‐based monitoring of anthropogenic impacts on the biodiversity and functioning of ecosystems is yet to be implemented by regulatory frameworks. Despite the broadly acknowledged potential of environmental genomics to this end, technical limitations and conceptual issues still stand in the way of its broad application by end‐users. In addition, the multiplicity of potential implementation strategies may contribute to a perception that the routine application of this methodology is premature or “in development”, hence restraining regulators from binding these tools into legal frameworks. Here, we review recent implementations of environmental genomics‐based methods, applied to the biomonitoring of ecosystems. By taking a general overview, without narrowing our perspective to particular habitats or groups of organisms, this paper aims to compare, review and discuss the strengths and limitations of four general implementation strategies of environmental genomics for monitoring: (a) Taxonomy‐based analyses focused on identification of known bioindicators or described taxa; (b) De novo bioindicator analyses; (c) Structural community metrics including inferred ecological networks; and (d) Functional community metrics (metagenomics or metatranscriptomics). We emphasise the utility of the three latter strategies to integrate meiofauna and microorganisms that are not traditionally utilised in biomonitoring because of difficult taxonomic identification. Finally, we propose a roadmap for the implementation of environmental genomics into routine monitoring programmes that leverage recent analytical advancements, while pointing out current limitations and future research needs.

Offshore Geological Hazards: Charting the Course of Progress and Future Directions - Gemma Ercilla; David Casas; Belén Alonso; Daniele Casalbore; Jesús Galindo-Zaldívar; Soledad García-Gil; Eleonora Martorelli; Juan-Tomás Vázquez; María Azpiroz-Zabala; Damien DoCouto; Ferran Estrada; Mᵃ Carmen Fernández-Puga; et al. (Oceans, 2021)
Offshore geological hazards can occur in any marine domain or environment and represent a serious threat to society, the economy, and the environment. Seismicity, slope sedimentary instabilities, submarine volcanism, fluid flow processes, and bottom currents are considered here because they are the most common hazardous processes; tsunamis are also examined because they are a secondary hazard generated mostly by earthquakes, slope instabilities, or volcanic eruptions. The hazards can co-occur and interact, inducing a cascading sequence of events, especially in certain contexts, such as tectonic indentations, volcanic islands, and canyon heads close to the coast. We analyze the key characteristics and main shortcomings of offshore geological hazards to identify their present and future directions for marine geoscience investigations of their identification and characterization. This review establishes that future research will rely on studies including a high level of multidisciplinarity. This approach, which also involves scientific and technological challenges, will require effective integration and interplay between multiscale analysis, mapping, direct deep-sea observations and testing, modelling, and linking offshore observations with onshore observations.

Behind the Scenes for the Designation of the Corales de Profundidad National Natural Park of Colombia - David Alonso; Martha Vides-Casado; Francisco Arias-Isaza; Hernando Zambrano; Emilio Rodriguez; Venus Rocha-Gutierrez; Pilar Herron; Anny Castillo (Frontiers in Marine Science, 2021)
Deep-water environments make up 64% of the world’s oceans (nearly 202 million km 2 ). In the past, the belief that this environment represented one of the most stable and unproductive ecosystems on the planet has been refuted by scientific research and the interest of potential productive sectors evaluating seabed resources. Human activities that threaten the health of deep-sea threats are uncontrolled and unregulated fishing, deep-sea mining, oil spills, marine litter, and climate change. With recent advances in technology, the study of deep-sea coral communities is a growing subject. The deep-sea corals are long-lived, slow-growing, and fragile systems, making them especially vulnerable to physical damage. In the last 40 years, Colombia has discovered these communities’ existence scarcely distributed in its territorial waters. A representative and irreplaceable sample of deep-sea coral formations triggered in 2013 the establishment of the Corales de Profundidad National Natural Park, a Marine Protected Area (MPA), which holds 40% of the marine biodiversity known in the Colombian Caribbean continental shelf-slope break. The MPA’s essential ecological value is the Madracis myriaster species’ presence as a primary habitat-forming organism, a unique habitat for the Caribbean and the world. Here we describe the MPA creation process in three phases. Firstly, in the provisioning phase, three main threats from human activities are identified. Secondly, in the preparation phase, the area’s conservation objectives and management category are defined, and the negotiation process with the fishing, communications, and oil and gas economic sectors is described. Lastly, in the designation phase, three MPA scenario proposals were evaluated, assessing the minimum distance, the possible effects of activities in the area as the main criteria for the buffer zone and the management of possible future impacts. As a result, the most extended boundary was adopted, guaranteeing these communities’ conservation despite the limited information to carry out a complete planning process. The MPA designation is considered the first experience of deep communities in the Southern Caribbean and an example that it is possible to have effective conservation agreements with economic sectors.

The characteristic time of ecological communities - Vicente J. Ontiveros; José A. Capitán; Emilio O. Casamayor; David Alonso (Ecology, 2021)
A simple description of temporal dynamics of ecological communities may help us understand how community assembly proceeds, predict ecological responses to environmental disturbances, and improve the performance of biological conservation actions. Although community changes take place at multiple temporal scales, the variation of species composition and richness over time across communities and habitats shows general patterns that may potentially reveal the main drivers of community dynamics. We used the simplest stochastic model of island biogeography to propose two quantities to characterize community dynamics: the community characteristic time , as a measure of the typical time scale of species‐richness change, and the characteristic Jaccard index , as a measure of temporal β diversity, that is, the variation of community composition over time. In addition, the community characteristic time, which sets the temporal scale at which null, noninteracting species assemblages operate, allowed us to define a relative sampling frequency (to the characteristic time). Here we estimate these quantities across microbial and macroscopic species assemblages to highlight two related results. First, we illustrated both characteristic time and Jaccard index and their relation with classic time‐series in ecology, and found that the most thoroughly sampled communities, relative to their characteristic time, presented the largest similarity between consecutive samples. Second, our analysis across a variety of habitats and taxa show that communities span a large range of species turnover, from potentially very fast (short characteristic times) to rather slow (long characteristic times) communities. This was in agreement with previous knowledge, but indicated that some habitats may have been sampled less frequently than required. Our work provides new perspectives to explore the temporal component in ecological studies and highlights the usefulness of simple approximations to the complex dynamics of ecological communities.

Spatio-Temporal Assessment of the European Hake (Merluccius merluccius) Recruits in the Northern Iberian Peninsula - Francisco Izquierdo; Iosu Paradinas; Santiago Cerviño; David Conesa; Alexandre Alonso-Fernández; Francisco Velasco; Izaskun Preciado; Antonio Punzón; Fran Saborido-Rey; Maria Grazia Pennino (Frontiers in Marine Science, 2021)
The protection of fish nurseries has been recognized as a useful tool to efficiently manage fisheries given that protected areas enhance the recruitment of target species. To identify and locate potential nursery areas, a solid understanding of species-environment relationships and their spatio-temporal dynamics is needed. Within this context, in this study we assess where European hake ( Merluccius merluccius ) recruits persistently aggregate in the northern continental shelf of the Iberian Peninsula. Hake recruit data collected during scientific trawl surveys between 2005 and 2016 were analyzed using Bayesian hurdle hierarchical spatio-temporal models, considering the environmental variables bathymetry, sea bottom temperature and salinity. Additionally, three different spatio-temporal structures (i.e., persistent, progressive, or opportunistic) were compared to assess the temporal persistence of nurseries over time. Among all the environmental variables analyzed, bathymetry was the most important. The preferential habitat of recruits was found to be within a bathymetric range of 120–200 m. Our findings clearly show that there is a temporally persistent main nursery located along the continental shelf of the Artabrian gulf (off La Coruña) in addition to several areas with high aggregations of hake recruits but with strong inter-annual variability. We argue that the analytical framework applied in this study allowed us to identify European hake nurseries in the northern continental shelf of the Iberian Peninsula, as well as their spatio-temporal fluctuations throughout the study period (2005–2016), and to assess which environmental factors, among bathymetry, sea bottom temperature and salinity, influence the occurrence and abundance of recruits in the study area. Results of our models also produce a new abundance index that could be useful for improving traditional stock assessment models.

Revisiting the Functional Basis of Sclerophylly Within the Leaf Economics Spectrum of Oaks: Different Roads to Rome - David Alonso-Forn; Domingo Sancho-Knapik; Juan Pedro Ferrio; José Javier Peguero-Pina; Amauri Bueno; Yusuke Onoda; Jeannine Cavender-Bares; Ülo Niinemets; Steven Jansen; Markus Riederer; Johannes H.C. Cornelissen; Yongfu Chai; et al. (Current Forestry Reports, 2020)

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Evaluating the potential of full‐waveform lidar for mapping pan‐tropical tree species richness - Suzanne M. Marselis; Katharine Abernethy; Alfonso Alonso; John Armston; Timothy R. Baker; Jean‐Francois Bastin; Jan Bogaert; Doreen S. Boyd; Pascal Boeckx; David F. R. P. Burslem; Robin Chazdon; David B. Clark; et al. (Global Ecology and Biogeography, 2020)
Aim Mapping tree species richness across the tropics is of great interest for effective conservation and biodiversity management. In this study, we evaluated the potential of full‐waveform lidar data for mapping tree species richness across the tropics by relating measurements of vertical canopy structure, as a proxy for the occupation of vertical niche space, to tree species richness. Location Tropics. Time period Present. Major taxa studied Trees. Methods First, we evaluated the characteristics of vertical canopy structure across 15 study sites using (simulated) large‐footprint full‐waveform lidar data (22 m diameter) and related these findings to in‐situ tree species information. Then, we developed structure–richness models at the local (within 25–50 ha plots), regional (biogeographical regions) and pan‐tropical scale at three spatial resolutions (1.0, 0.25 and 0.0625 ha) using Poisson regression. Results The results showed a weak structure–richness relationship at the local scale. At the regional scale (within a biogeographical region) a stronger relationship between canopy structure and tree species richness across different tropical forest types was found, for example across Central Africa and in South America [ R 2 ranging from .44–.56, root mean squared difference as a percentage of the mean (RMSD%) ranging between 23–61%]. Modelling the relationship pan‐tropically, across four continents, 39% of the variation in tree species richness could be explained with canopy structure alone ( R 2 = .39 and RMSD% = 43%, 0.25‐ha resolution). Main conclusions Our results may serve as a basis for the future development of a set of structure–richness models to map high resolution tree species richness using vertical canopy structure information from the Global Ecosystem Dynamics Investigation (GEDI). The value of this effort would be enhanced by access to a larger set of field reference data for all tropical regions. Future research could also support the use of GEDI data in frameworks using environmental and spectral information for modelling tree species richness across the tropics.

10th Anniversary of the European Association for Predictive, Preventive and Personalised (3P) Medicine - EPMA World Congress Supplement 2020 - Olga Golubnitschaja; Ondrej Topolcan; Radek Kucera; Vincenzo Costigliola; M. Akopyan; S. N. Akulov; O Alexandrova; Angel Alonso; Russell J. Andrews; A Assuane Duarte; O. Azarova; Maximilian Babel; et al. (EPMA Journal, 2020)
In 2019, the EPMA celebrated its 10th anniversary at the 5th World Congress in Pilsen, Czech Republic. The history of the International Professional Network dedicated to Predictive, Preventive and Personalised Medicine (PPPM / 3PM) is rich in achievements. Facing the coronavirus COVID-19 pandemic it is getting evident globally that the predictive approach, targeted prevention and personalisation of medical services is the optimal paradigm in healthcare demonstrating the high potential to save lives and to benefit the society as a whole. The EPMA World Congress Supplement 2020 highlights advances in 3P medicine.

Experimental approaches to the development of use-wear traces on volcanic rocks: basalts - Patricia Bello-Alonso; Joseba Rios-Garaizar; Joaquín Panera; David Manuel Martín-Perea; Susana Rubio-Jara; Alfredo Pérez-González; Raquel Rojas-Mendoza; Manuel Domínguez-Rodrigo; Enrique Baquedano; Manuel Santonja (Archaeological and Anthropological Sciences, 2020)

First confirmed report of Colletotrichum coccodes causing black dot on potato in Mexico - Juan Luis Pérez-Mora; David Alonso Cota-Rodríguez; Edgar Edel Rodríguez-Palafox; Elizabeth García-León; Hugo Beltrán-Peña; Nelson Bernardi Lima; Juan Manuel Tovar-Pedraza (Journal of Plant Diseases and Protection, 2020)

Estimation of moult duration in birds with suspended moults: the case of the Red Crossbill and its relation to reproduction - Blanca Fernández-Eslava; Daniel Alonso; David Galicia; Juan Arizaga (Journal of Ornithology, 2020)

Climate‐induced changes in the suitable habitat of cold‐water corals and commercially important deep‐sea fishes in the North Atlantic - Telmo Morato; José‐Manuel González‐Irusta; Carlos Dominguez‐Carrió; Chih‐Lin Wei; Andrew Davies; Andrew K. Sweetman; Gerald H. Taranto; Lindsay Beazley; Ana García‐Alegre; Anthony Grehan; Pascal Laffargue; Francisco Javier Murillo; et al. (Global Change Biology, 2020)
The deep sea plays a critical role in global climate regulation through uptake and storage of heat and carbon dioxide. However, this regulating service causes warming, acidification and deoxygenation of deep waters, leading to decreased food availability at the seafloor. These changes and their projections are likely to affect productivity, biodiversity and distributions of deep‐sea fauna, thereby compromising key ecosystem services. Understanding how climate change can lead to shifts in deep‐sea species distributions is critically important in developing management measures. We used environmental niche modelling along with the best available species occurrence data and environmental parameters to model habitat suitability for key cold‐water coral and commercially important deep‐sea fish species under present‐day (1951–2000) environmental conditions and to project changes under severe, high emissions future (2081–2100) climate projections (RCP8.5 scenario) for the North Atlantic Ocean. Our models projected a decrease of 28%–100% in suitable habitat for cold‐water corals and a shift in suitable habitat for deep‐sea fishes of 2.0°–9.9° towards higher latitudes. The largest reductions in suitable habitat were projected for the scleractinian coral Lophelia pertusa and the octocoral Paragorgia arborea , with declines of at least 79% and 99% respectively. We projected the expansion of suitable habitat by 2100 only for the fishes Helicolenus dactylopterus and Sebastes mentella (20%–30%), mostly through northern latitudinal range expansion. Our results projected limited climate refugia locations in the North Atlantic by 2100 for scleractinian corals (30%–42% of present‐day suitable habitat), even smaller refugia locations for the octocorals Acanella arbuscula and Acanthogorgia armata (6%–14%), and almost no refugia for P. arborea . Our results emphasize the need to understand how anticipated climate change will affect the distribution of deep‐sea species including commercially important fishes and foundation species, and highlight the importance of identifying and preserving climate refugia for a range of area‐based planning and management tools.

Levels, spatial distribution, risk assessment, and sources of environmental contamination vectored by road dust in Cienfuegos (Cuba) revealed by chemical and C and N stable isotope compositions - Yasser Morera-Gómez; Carlos Manuel Alonso-Hernández; Jesús Miguel Santamaría; David Elustondo; Esther Lasheras; David Widory (Environmental Science and Pollution Research, 2020)

Evaluation of the Alfred™ turbidity monitoring system (Alifax®) following sonication in the diagnosis of central venous catheter colonization - Beatriz Alonso; María Consuelo Latorre; Raquel Cruces; David Ampuero; Laura Haces; Pablo Martín-Rabadán; Carlos Sánchez-Carrillo; Belén Rodríguez; Emilio Bouza; Patricia Muñoz; María Guembe (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Assimilation of dietary nitrogen supplied by fish meal and microalgal biomass from Spirulina (Arthrospira platensis) and Nannochloropsis oculata in shrimp Litopenaeus vannamei fed compound diets - Julián Gamboa-Delgado; Yonatan Izahí Morales-Navarro; Martha G. Nieto-López; David Alonso Villarreal-Cavazos; Lucía Elizabeth Cruz-Suárez (Journal of Applied Phycology, 2019)

Evaluating the Fit of Co-management for Small-Scale Fisheries Governance in Timor-Leste - Alexander Tilley; Kimberley J. Hunnam; David J. Mills; Dirk J. Steenbergen; Hugh Govan; Enrique Alonso-Poblacion; Matthew Roscher; Mario Pereira; Pedro Rodrigues; Teresa Amador; Agustinha Duarte; Mario Gomes; et al. (Frontiers in Marine Science, 2019)

Passive sampling as a feasible tool for mapping and model evaluation of the spatial distribution of nitrogen oxides in the city of Curitiba, Brazil - Erika Felix; Lars Gidhagen; Marcelo F. Alonso; Everaldo P. Nahirny; Bruno L. Alves; David Segersson; Jorge H. Amorim (Air Quality, Atmosphere & Health, 2019)

Anthropization level of Lascaux Cave microbiome shown by regional‐scale comparisons of pristine and anthropized caves - Lise Alonso; Thomas Pommier; Bernard Kaufmann; Audrey Dubost; David Chapulliot; Jeanne Doré; Christophe J. Douady; Yvan Moënne‐Loccoz (Molecular Ecology, 2019)
Limestone areas across the world develop karstic caves, which are populated by a wide range of macro‐ and microorganisms. Many of these caves display Paleolithic art or outstanding speleothems, and in the last century they have been subjected to anthropization due to touristic management and intense human frequentation. Despite their cultural importance and associated conservation issues, the impact of anthropization on cave biodiversity is not known. Here, we show that anthropization is associated with specific cave biota modifications. We compared diversity in four pristine caves, four anthropized show caves, and the iconic Lascaux Cave with even stronger anthropization. The predominant microbial higher taxa were the same in all caves, but the most anthropized cave (Lascaux) was unique as it differed from the eight others by a higher proportion of Bacteroidetes bacteria and the absence of Euryarchaeota and Woesearchaeota archaea. Anthropization resulted in lower diversity and altered community structure for bacteria and archaea on cave walls, especially in Lascaux, but with a more limited effect on microeukaryotes and arthropods. Our findings fill a key gap in our understanding of the response of karstic communities to anthropization, by revealing that tourism‐related anthropization impacts on the prokaryotic microbiome rather than on eukaryotic residents, and that it shapes cave biota irrespective of cave natural features.

A participatory epidemiological study of major cattle diseases amongst Maasai pastoralists living in wildlife-livestock interfaces in Maasai Mara, Kenya - Daniel Nthiwa; Silvia Alonso; David Odongo; Eucharia Kenya; Bernard Bett (Tropical Animal Health and Production, 2019)

Unusual occurrences of fishes along the Northeast Atlantic: new biological and distributional data - RAFAEL BAÑÓN; RAQUEL TEJERINA; XESÚS MORALES; ALEXANDRE ALONSO-FERNÁNDEZ; DAVID BARROS-GARCÍA; ALEJANDRO DE CARLOS (Mediterranean Marine Science, 2019)
The occurrences of 13 specimens belonging to 9 species of little known marine fishes in the Northeast Atlantic in 2017 and 2018 are reported. Information about the morphology and new findings of Decapterus tabl and Decapterus macarellus (Carangidae), Kyphosus vaigiensis (Kyphosidae), Remora osteochir (Echeneidae), Antigonia capros (Caproidae), Hyperoglyphe perciformis (Centrolophidae), Halobatrachus didactylus (Batrachoididae), Parapristipoma octolineatum (Haemulidae) and Zu cristatus (Trachypteridae) are reported in different locations, where they are categorized as unusual or rare. Morphometric and meristic parameters confirm the identification to species level of each specimen, also supported by DNA barcoding. Histological examination of reproductive tissue is carried out in four specimens to know the sex and their reproductive stage. All species are known from other areas of the Atlantic Ocean, but these findings are an important contribution to understanding their biology and distribution. These include a new northernmost record of Remora osteochir and Decapterus tabl in the eastern Atlantic and the first records of Antigonia capros, Hyperoglyphe perciformis, Halobatrachus didactylus and Parapristipoma octolineatum from Galician waters.

Direct and indirect effects of climate on richness drive the latitudinal diversity gradient in forest trees - Chengjin Chu; James A. Lutz; Kamil Král; Tomáš Vrška; Xue Yin; Jonathan A. Myers; Iveren Abiem; Alfonso Alonso; Norm Bourg; David F.R.P. Burslem; Min Cao; Hazel Chapman; et al. (Ecology Letters, 2019)
Climate is widely recognised as an important determinant of the latitudinal diversity gradient. However, most existing studies make no distinction between direct and indirect effects of climate, which substantially hinders our understanding of how climate constrains biodiversity globally. Using data from 35 large forest plots, we test hypothesised relationships amongst climate, topography, forest structural attributes (stem abundance, tree size variation and stand basal area) and tree species richness to better understand drivers of latitudinal tree diversity patterns. Climate influences tree richness both directly, with more species in warm, moist, aseasonal climates and indirectly, with more species at higher stem abundance. These results imply direct limitation of species diversity by climatic stress and more rapid (co‐)evolution and narrower niche partitioning in warm climates. They also support the idea that increased numbers of individuals associated with high primary productivity are partitioned to support a greater number of species.

Genomic study of a novel magnetotactic Alphaproteobacteria uncovers the multiple ancestry of magnetotaxis - Caroline L. Monteil; Guy Perrière; Nicolas Menguy; Nicolas Ginet; Béatrice Alonso; Nicolas Waisbord; Stéphane Cruveiller; David Pignol; Christopher T. Lefèvre (Environmental Microbiology, 2018)
Summary Ecological and evolutionary processes involved in magnetotactic bacteria (MTB) adaptation to their environment have been a matter of debate for many years. Ongoing efforts for their characterization are progressively contributing to understand these processes, including the genetic and molecular mechanisms responsible for biomineralization. Despite numerous culture‐independent MTB characterizations, essentially within the Proteobacteria phylum, only few species have been isolated in culture because of their complex growth conditions. Here, we report a newly cultivated magnetotactic, microaerophilic and chemoorganoheterotrophic bacterium isolated from the Mediterranean Sea in Marseille, France: Candidatus Terasakiella magnetica strain PR‐1 that belongs to an Alphaproteobacteria genus with no magnetotactic relative. By comparing the morphology and the whole genome shotgun sequence of this MTB with those of closer relatives, we brought further evidence that the apparent vertical ancestry of magnetosome genes suggested by previous studies within Alphaproteobacteria hides a more complex evolutionary history involving horizontal gene transfers and/or duplication events before and after the emergence of Magnetospirillum , Magnetovibrio and Magnetospira genera. A genome‐scale comparative genomics analysis identified several additional candidate functions and genes that could be specifically associated to MTB lifestyle in this class of bacteria.

Geographic range expansion of Ephippion guttifer (Tetraodontidae) in the north‐eastern Atlantic - Rafael Bañón; Alexandre Alonso‐Fernández; David Barros‐García; María‐Berta Rios; Alejandro de Carlos (Journal of Fish Biology, 2018)
The first record of the prickly puffer Ephippion guttifer (Tetraodontidae) from Galician waters (north‐west Spain) is reported based on a male specimen of 570 mm total length ( L T ) caught in the Ría de Vigo. Morphometric, meristic and DNA barcode data confirmed the identification. Histological examination of reproductive tissue was carried out in this species for the first time, showing a mature male in an actively spawning phase. A historical revision invalidates a previous record and establishes this as the northernmost confirmed capture ever reported in the north‐eastern Atlantic Ocean.

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Evaluation of the performance of three tenodesis techniques for the treatment of scapholunate instability: flexion-extension and radial-ulnar deviation - Teresa Alonso-Rasgado; Qing-Hang Zhang; David Jimenez-Cruz; Colin Bailey; Elizabeth Pinder; Avanthi Mandaleson; Sumedh Talwalkar (Medical & Biological Engineering & Computing, 2018)

Full genome sequences are key to disclose RHDV2 emergence in the Macaronesian islands - Ana M. Lopes; Jose Blanco-Aguiar; Aaron Martín-Alonso; Manuel Leitão; Pilar Foronda; Marco Mendes; David Gonçalves; Joana Abrantes; Pedro J. Esteves (Virus Genes, 2018)

Reply to comment from Dominguez Cerdeña et al. (2017) on “Geochemical evidences of seismo-volcanic unrests at the NW rift-zone of Tenerife, Canary Islands, inferred from diffuse CO2 emission” by Hernández et al. [Bull. Volcanol. (2017), 79:30] - Pedro A. Hernández; Germán Padilla; José Barrancos; Gladys Melián; Eleazar Padrón; María Asensio-Ramos; Fátima Rodríguez; Nemesio Pérez; Mar Alonso; David Calvo (Bulletin of Volcanology, 2018)

Genome-Wide Association Analysis of the Sense of Smell in U.S. Older Adults: Identification of Novel Risk Loci in African-Americans and European-Americans - Jing Dong; Annah Wyss; Jingyun Yang; T. Ryan Price; Aude Nicolas; Michael Nalls; Greg Tranah; Nora Franceschini; Zongli Xu; Claudia Schulte; Alvaro Alonso; Steven R. Cummings; et al. (Molecular Neurobiology, 2017)

Quantitative study on nitrogen deposition and canopy retention in Mediterranean evergreen forests - Anna Avila; Laura Aguillaume; Sheila Izquieta-Rojano; Héctor García-Gómez; David Elustondo; Jesús Miguel Santamaría; Rocío Alonso (Environmental Science and Pollution Research, 2017)

Substratum karstificability, dispersal and genetic structure in a strictly subterranean beetle - Valeria Rizzo; David Sánchez‐Fernández; Rocío Alonso; Josep Pastor; Ignacio Ribera (Journal of Biogeography, 2017)
Aim The deep subterranean environment is an ideal system to test the effect of physical constraints on the ecology and evolution of species, as it is very homogeneous and with simple communities. We studied the effect of substratum karstificability in the dispersal of the strictly subterranean Troglocharinus ferreri (Reitter) (Coleoptera, Leiodidae) by comparing the genetic diversity and structure of populations in limestone (more soluble) and dolostone (less soluble) in the same karstic system. Location Troglocharinus ferreri is only known from c . 100 vertical shafts in an area of 2 SW of Barcelona (Spain). Methods We sequenced mitochondrial and nuclear markers of a representative sample to identify main lineages within T. ferreri and estimate their temporal origin, and used mitochondrial data of 129 specimens from 41 caves to reconstruct their demographic history and estimate dispersal among caves. Results Troglocharinus ferreri diverged from its sister in the Early Pliocene, with an initial divergence of the sampled populations in the Early Pleistocene. The best demographic model was a constant population size with a fast population increase in the middle Pleistocene. The ancestral population was likely in limestone, with a probability of transition from limestone to dolostone triple to that from dolostone to limestone, suggesting a higher permeability of limestone to the transit of individuals. Populations in dolostone caves had lower gene flow between them and a stronger isolation by distance, although the low genetic variability for the studied markers and the lower abundance of dolostone caves decreased the statistical power of the analyses. Main conclusions Our results point to the physical characteristic of the substratum as a determinant of dispersal and gene flow, potentially conditioning the long‐term evolution of subterranean biodiversity.

Defining the importance of landscape metrics for large branchiopod biodiversity and conservation: the case of the Iberian Peninsula and Balearic Islands - Jordi Sala; Stéphanie Gascón; David Cunillera-Montcusí; Miguel Alonso; Francisco Amat; Luís Cancela da Fonseca; Margarida Cristo; Margarita Florencio; Juan García-de-Lomas; Margarida Machado; Maria Rosa Miracle; Alexandre Miró; et al. (Hydrobiologia, 2017)

New evidence of bones used as fuel in the Gravettian level at Coímbre cave, northern Iberian Peninsula - José Yravedra; David Álvarez-Alonso; Verónica Estaca-Gómez; Pablo López-Cisneros; Álvaro Arrizabalaga; Mikelo Elorza; Ma. José Iriarte; Jesús F. Jordá Pardo; Carmen Sesé; Paloma Uzquiano (Archaeological and Anthropological Sciences, 2017)

Non-intrusive Assessment of Photosystem II and Photosystem I in Whole Coral Tissues - Milán Szabó; Anthony W. D. Larkum; David J. Suggett; Imre Vass; László Sass; Barry Osmond; Alonso Zavafer; Peter J. Ralph; Wah S. Chow (Frontiers in Marine Science, 2017)

Geochemical evidences of seismo-volcanic unrests at the NW rift zone of Tenerife, Canary Islands, inferred from diffuse CO2 emission - Pedro A. Hernández; Germán Padilla; José Barrancos; Gladys Melián; Eleazar Padrón; María Asensio-Ramos; Fátima Rodríguez; Nemesio Pérez; Mar Alonso; David Calvo (Bulletin of Volcanology, 2017)

Small cryptopredators contribute to high predation rates on coral reefs - Christopher H. R. Goatley; Alonso González-Cabello; David R. Bellwood (Coral Reefs, 2017)

Multichannel Seismic Imaging of the Rivera Plate Subduction at the Seismogenic Jalisco Block Area (Western Mexican Margin) - Rafael Bartolome; Estefanía Górriz; Juanjo Dañobeitia; Diego Cordoba; David Martí; Alejandra L. Cameselle; Francisco Núñez-Cornú; William L. Bandy; Carlos A. Mortera-Gutiérrez; Diana Nuñez; Arturo Castellón; Jose Luis Alonso (Pure and Applied Geophysics, 2016)

The macroecology of infectious diseases: a new perspective on global‐scale drivers of pathogen distributions and impacts - Patrick R. Stephens; Sonia Altizer; Katherine F. Smith; A. Alonso Aguirre; James H. Brown; Sarah A. Budischak; James E. Byers; Tad A. Dallas; T. Jonathan Davies; John M. Drake; Vanessa O. Ezenwa; Maxwell J. Farrell; et al. (Ecology Letters, 2016)
Identifying drivers of infectious disease patterns and impacts at the broadest scales of organisation is one of the most crucial challenges for modern science, yet answers to many fundamental questions remain elusive. These include what factors commonly facilitate transmission of pathogens to novel host species, what drives variation in immune investment among host species, and more generally what drives global patterns of parasite diversity and distribution? Here we consider how the perspectives and tools of macroecology, a field that investigates patterns and processes at broad spatial, temporal and taxonomic scales, are expanding scientific understanding of global infectious disease ecology. In particular, emerging approaches are providing new insights about scaling properties across all living taxa, and new strategies for mapping pathogen biodiversity and infection risk. Ultimately, macroecology is establishing a framework to more accurately predict global patterns of infectious disease distribution and emergence.

Reconstructing ancient Mediterranean crossroads in Deronectes diving beetles - David García‐Vázquez; David T. Bilton; Rocío Alonso; Cesar J. Benetti; Josefina Garrido; Luis F. Valladares; Ignacio Ribera (Journal of Biogeography, 2016)
Aim To reconstruct the evolutionary history of a genus of freshwater beetle with a pan‐Mediterranean distribution, to test classic hypotheses which proposed a Miocene origin for groups with high biodiversity in the Iberian and Anatolian peninsulas. Location Mediterranean basin. Methods We sequenced four mitochondrial and one nuclear gene from 51 specimens of 30 of the c . 60 extant species of Deronectes (Dytiscidae), all typical of mid‐mountain streams from North Africa and Iberia over most of Europe to the Middle East. We used maximum likelihood, Bayesian probabilities with an a priori evolutionary rate and a dispersal–extinction–cladogenesis model to reconstruct their biogeographical history. Results Deronectes has two major lineages which originated in the mid Miocene; one including mostly eastern and another mainly western and central Mediterranean species. From these two areas, range expansions, mainly at the end of the Miocene and beginning of the Pliocene, resulted in the many species groups and some of the extant species of the genus. Most of the current diversity and distributions are, however, of Plio‐Pleistocene origin, particularly in widespread European species. Main conclusions In line with traditional hypotheses, we found an ancient division between eastern and western Mediterranean lineages of Deronectes , likely resulting from the isolation of Europe west of the Alps from the Balkans and Anatolia during the early‐middle Miocene. The history of the genus was strongly influenced by major geological and climatic events, with successive cycles of fragmentation and subsequent eastward and westward range expansions, resulting in a steady accumulation of species across the basin. Most of these range movements took place through the north side of the Mediterranean, with only local displacements in the south during the Messinian salinity crisis and a recent (Pleistocene) colonization of the Italian Peninsula, which remained largely submerged through most of the genus’ evolutionary history.

Consequences of extreme life history traits on population persistence: do short-lived gobies face demographic bottlenecks? - Carine D. Lefèvre; Kirsty L. Nash; Alonso González-Cabello; David R. Bellwood (Coral Reefs, 2016)

Latitudinal regionalization of epibenthic macroinvertebrate communities on rocky reefs in the Gulf of California - Karol Ulate; Carlos Sánchez; Alexandra Sánchez-Rodríguez; David Alonso; Octavio Aburto-Oropeza; Leonardo Huato-Soberanis (Marine Biology Research, 2016)

Atmospheric pollutants in peri-urban forests of Quercus ilex: evidence of pollution abatement and threats for vegetation - Héctor García-Gómez; Laura Aguillaume; Sheila Izquieta-Rojano; Fernando Valiño; Anna Àvila; David Elustondo; Jesús M. Santamaría; Andrés Alastuey; Héctor Calvete-Sogo; Ignacio González-Fernández; Rocío Alonso (Environmental Science and Pollution Research, 2016)

Prevalence of bovine subclinical mastitis, its etiology and diagnosis of antibiotic resistance of dairy farms in four municipalities of a tropical region of Mexico - Jaime Olivares-Pérez; Ahmed Eid Kholif; Saul Rojas-Hernández; Mona Mohamed Mohamed Yasseen Elghandour; Abdelfattah Zeidan Mohamed Salem; Adrian Zaragoza Bastida; David Velázquez-Reynoso; Moisés Cipriano-Salazar; Luis Miguel Camacho-Díaz; María Uxúa Alonso-Fresán; Nicolas DiLorenzo (Tropical Animal Health and Production, 2015)

Anti-metastatic action of FAK inhibitor OXA-11 in combination with VEGFR-2 signaling blockade in pancreatic neuroendocrine tumors - Ingrid Moen; Matthew Gebre; Vanesa Alonso-Camino; Debbie Chen; David Epstein; Donald M. McDonald (Clinical & Experimental Metastasis, 2015)

Connecting Groundwater and Surface Water Sources in Groundwater Dependent Coastal Wetlands and Estuaries: Sian Ka’an Biosphere Reserve, Quintana Roo, Mexico - David Lagomasino; René M. Price; Jorge Herrera-Silveira; Fernando Miralles-Wilhelm; Gonzalo Merediz-Alonso; Yadira Gomez-Hernandez (Estuaries and Coasts, 2015)

Fish community reassembly after a coral mass mortality: higher trophic groups are subject to increased rates of extinction - David Alonso; Aleix Pinyol‐Gallemí; Teresa Alcoverro; Rohan Arthur (Ecology Letters, 2015)
Since Gleason and Clements, our understanding of community dynamics has been influenced by theories emphasising either dispersal or niche assembly as central to community structuring. Determining the relative importance of these processes in structuring real‐world communities remains a challenge. We tracked reef fish community reassembly after a catastrophic coral mortality in a relatively unfished archipelago. We revisited the stochastic model underlying MacArthur and Wilson's Island Biogeography Theory, with a simple extension to account for trophic identity. Colonisation and extinction rates calculated from decadal presence‐absence data based on (1) species neutrality, (2) trophic identity and (3) site‐specificity were used to model post‐disturbance reassembly, and compared with empirical observations. Results indicate that species neutrality holds within trophic guilds, and trophic identity significantly increases overall model performance. Strikingly, extinction rates increased clearly with trophic position, indicating that fish communities may be inherently susceptible to trophic downgrading even without targeted fishing of top predators.

Apoptosis for prediction of radiotherapy late toxicity: lymphocyte subset sensitivity and potential effect of TP53 Arg72Pro polymorphism - María J. Fuentes-Raspall; Isabel Caragol; Carmen Alonso; Teresa Ramón y Cajal; David Fisas; Alejandro Seoane; Nerea Carvajal; Sandra Bonache; Orland Díez; Sara Gutiérrez-Enríquez (Apoptosis, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Ichthyofauna of the Selvagens Islands. Do small coastal areas show high species richness in the northeastern Atlantic? - Frederico Almada; David Abecasis; David Villegas-Ríos; Sofia Henriques; Miguel P. Pais; Marisa Batista; Bárbara Horta e Costa; Joana Martins; Inês Tojeira; Nuno Vasco Rodrigues; Ricardo Araújo; Miguel Souto; et al. (Marine Biology Research, 2015)

Calcium carbonate precipitation by heterotrophic bacteria isolated from biofilms formed on deteriorated ignimbrite stones: influence of calcium on EPS production and biofilm formation by these isolates - Angélica López-Moreno; José David Sepúlveda-Sánchez; Elia Mercedes Mercedes Alonso Guzmán; Sylvie Le Borgne (Biofouling, 2014)

Sex-influence of nicotine and nitric oxide on motor coordination and anxiety-related neurophysiological responses - Rodrigo Muñoz-Castañeda; David Díaz; Carmelo A. Ávila-Zarza; José R. Alonso; Eduardo Weruaga (Psychopharmacology, 2014)

Acetochlor Persistence in Surface and Subsurface Soil Samples - Rubem S. Oliveira; William C. Koskinen; Carrie D. Graff; James L. Anderson; David J. Mulla; Edward A. Nater; Diego G. Alonso (Water, Air, & Soil Pollution, 2013)

Erratum to: Haemodynamic responses to dehydration in the resting and exercising human leg - James Pearson; Kameljit K. Kalsi; Eric J. Stöhr; David A. Low; Horace Barker; Leena Ali; José González-Alonso (European Journal of Applied Physiology, 2013)

Rheological control on the tectonic evolution of a continental suture zone: the Variscan example from NW Iberia (Spain) - Rubén Díez Fernández; David A. Foster; Juan Gómez Barreiro; Montserrat Alonso-García (International Journal of Earth Sciences, 2013)

Haemodynamic responses to dehydration in the resting and exercising human leg - James Pearson; Kameljit K. Kalsi; Eric J. Stöhr; David A. Low; Horace Barker; Leena Ali; José González-Alonso (European Journal of Applied Physiology, 2013)

Climate change and infectious diseases: Can we meet the needs for better prediction? - Xavier Rodó; Mercedes Pascual; Francisco J. Doblas-Reyes; Alexander Gershunov; Dáithí A. Stone; Filippo Giorgi; Peter J. Hudson; James Kinter; Miquel-Àngel Rodríguez-Arias; Nils Ch. Stenseth; David Alonso; Javier García-Serrano; et al. (Climatic Change, 2013)

Investigating the kinematics of local thrust sheet rotation in the limb of an orocline: a paleomagnetic and structural analysis of the Esla tectonic unit, Cantabrian–Asturian Arc, NW Iberia - Arlo Brandon Weil; Gabriel Gutiérrez-Alonso; David Wicks (International Journal of Earth Sciences, 2013)

Regional-scale airborne electromagnetic surveying of the Yucatan karst aquifer (Mexico): geological and hydrogeological interpretation - Bibi R. N. Gondwe; David Ottowitz; Robert Supper; Klaus Motschka; Gonzalo Merediz-Alonso; Peter Bauer-Gottwein (Hydrogeology Journal, 2012)

Coral recovery may not herald the return of fishes on damaged coral reefs - David R. Bellwood; Andrew H. Baird; Martial Depczynski; Alonso González-Cabello; Andrew S. Hoey; Carine D. Lefèvre; Jennifer K. Tanner (Oecologia, 2012)

CCL27–CCR10 and CXCL12–CXCR4 chemokine ligand-receptor mRNA expression ratio: new predictive factors of tumor progression in cutaneous malignant melanoma - Carlos Monteagudo; David Ramos; Ana Pellín-Carcelén; Rosario Gil; Robert C. Callaghan; José M. Martín; Vicent Alonso; Amelia Murgui; Lara Navarro; Silvia Calabuig; José Antonio López-Guerrero; Esperanza Jordá; et al. (Clinical & Experimental Metastasis, 2012)

Species formation and geographical range evolution in a genus of Central American cloud forest salamanders ( Dendrotriton ) - Sean M. Rovito; David B. Wake; Theodore J. Papenfuss; Gabriela Parra‐Olea; Antonio Muñoz‐Alonso; Carlos R. Vásquez‐Almazán (Journal of Biogeography, 2012)
Aim Montane Central America offers an ideal system for testing geographical hypotheses of species diversification. We examined how the complex geological history of Nuclear Central America has shaped the diversification of a genus of cloud‐forest‐inhabiting salamanders ( Dendrotriton ). We applied parametric models of geographical range evolution to determine the predominant mode of species formation within the genus and to test existing hypotheses of geographical species formation in the region. Location Montane cloud forests of Nuclear Central America. Methods We estimated a species tree for Dendrotriton using a multi‐locus DNA sequence data set and several coalescent methods, and performed molecular dating for divergence events within the genus. We then applied the species‐tree estimate to a likelihood‐based time‐stratified model of geographical range evolution, based on current species distributions and available geological information for Central America. Results Species trees from all methods contain two groups, one corresponding to species from the Sierra de los Cuchumatanes and the other containing all remaining species. In most cases, species formation within the genus involved an even division of the geographical range of the ancestral species between descendant species. The ancestor of extant Dendrotriton species was estimated to have occurred in either the Sierra de los Cuchumatanes or the Sierra Madre de Chiapas, and both of these areas appear to have been important for diversification within the genus. The single species found in the Quaternary‐age Guatemalan volcanic cordillera dispersed to the volcanoes from an older highland area. Main conclusions Models of geographical range evolution, when combined with robust species‐tree estimates, provide insight into the historical biogeography of taxa not available from phylogenies or distributional data alone. Vicariant species formation, rather than peripatric or gradient speciation, appears to have been the dominant process of diversification, with most divergence events occurring within or between ancient highland areas. The apparent dispersal of Dendrotriton to the Quaternary‐age volcanoes raises the possibility that the rich salamander community there is composed of species that dispersed from geologically older areas. The Motagua Valley appears not to have been as important in vicariant species formation within Dendrotriton as it is within other groups.

Global patterns of stream detritivore distribution: implications for biodiversity loss in changing climates - Luz Boyero; Richard G. Pearson; David Dudgeon; Verónica Ferreira; Manuel A. S. Graça; Mark O. Gessner; Andrew J. Boulton; Eric Chauvet; Catherine M. Yule; Ricardo J. Albariño; Alonso Ramírez; Julie E. Helson; et al. (Global Ecology and Biogeography, 2012)
Aim We tested the hypothesis that shredder detritivores, a key trophic guild in stream ecosystems, are more diverse at higher latitudes, which has important ecological implications in the face of potential biodiversity losses that are expected as a result of climate change. We also explored the dependence of local shredder diversity on the regional species pool across latitudes, and examined the influence of environmental factors on shredder diversity. Location World‐wide (156 sites from 17 regions located in all inhabited continents at latitudes ranging from 67° N to 41° S). Methods We used linear regression to examine the latitudinal variation in shredder diversity at different spatial scales: alpha (α), gamma (γ) and beta (β) diversity. We also explored the effect of γ‐diversity on α‐diversity across latitudes with regression analysis, and the possible influence of local environmental factors on shredder diversity with simple correlations. Results Alpha diversity increased with latitude, while γ‐ and β‐diversity showed no clear latitudinal pattern. Temperate sites showed a linear relationship between γ‐ and α‐diversity; in contrast, tropical sites showed evidence of local species saturation, which may explain why the latitudinal gradient in α‐diversity is not accompanied by a gradient in γ‐diversity. Alpha diversity was related to several local habitat characteristics, but γ‐ and β‐diversity were not related to any of the environmental factors measured. Main conclusions Our results indicate that global patterns of shredder diversity are complex and depend on spatial scale. However, we can draw several conclusions that have important ecological implications. Alpha diversity is limited at tropical sites by local factors, implying a higher risk of loss of key species or the whole shredder guild (the latter implying the loss of trophic diversity). Even if regional species pools are not particularly species poor in the tropics, colonization from adjacent sites may be limited. Moreover, many shredder species belong to cool‐adapted taxa that may be close to their thermal maxima in the tropics, which makes them more vulnerable to climate warming. Our results suggest that tropical streams require specific scientific attention and conservation efforts to prevent loss of shredder biodiversity and serious alteration of ecosystem processes.

Functional analysis in Arabidopsis of FsPTP1, a tyrosine phosphatase from beechnuts, reveals its role as a negative regulator of ABA signaling and seed dormancy and suggests its involvement in ethylene signaling modulation - Ana Alonso-Ramírez; Dolores Rodríguez; David Reyes; Jesús A. Jiménez; Gregorio Nicolás; Carlos Nicolás (Planta, 2011)

Hyaluronic Acid/Chitosan-g-Poly(ethylene glycol) Nanoparticles for Gene Therapy: An Application for pDNA and siRNA Delivery - Manuela Raviña; Eva Cubillo; David Olmeda; Ramón Novoa-Carballal; Eduardo Fernandez-Megia; Ricardo Riguera; Alejandro Sánchez; Amparo Cano; María José Alonso (Pharmaceutical Research, 2010)

Uptake of predictive testing among relatives of BRCA1 and BRCA2 families: a multicenter study in northeastern Spain - Judit Sanz; Teresa Ramón y Cajal; Asunción Torres; Esther Darder; Neus Gadea; Angela Velasco; Daniel Fortuny; Consol López; David Fisas; Joan Brunet; M. Carmen Alonso; Judith Balmaña (Familial Cancer, 2010)

Interactive Effects of Three Ecosystem Engineers on Infiltration in a Semi-Arid Mediterranean Grassland - David J. Eldridge; Matthew A. Bowker; Fernando T. Maestre; Patricia Alonso; Rebecca L. Mau; Jorge Papadopoulos; Adrián Escudero (Ecosystems, 2010)

Sex differences in antipredator tail-waving displays of the diurnal yellow-headed gecko Gonatodes albogularis from tropical forests of Colombia - Martha L. Bohórquez Alonso; Jorge Martínez Cotrina; David Aguilar Pardo; Enrique Font; Miguel Molina-Borja (Journal of Ethology, 2010)

Local ecological impacts of regional biodiversity on reef fish assemblages - Alonso González‐Cabello; David R. Bellwood (Journal of Biogeography, 2009)
Aim We examined comparative data for cryptobenthic reef fishes to determine how variation in regional species richness relates to local species richness, abundance, and taxonomic and trophic composition, and to test whether systems with higher species richness exhibit finer habitat partitioning. Locations Lizard Island, Great Barrier Reef (GBR), Australia; Bahía de Loreto, Gulf of California (GoC), Mexico. Methods Cryptobenthic reef fish assemblages from four habitats (coral heads, rubble, and horizontal and vertical surfaces of boulders) were collected using clove oil. Differences in density, species richness and biomass were examined between regions and among habitats. Habitat associations were identified for each habitat/location based on multivariate ordination, and the statistical significance of patterns was tested using analysis of similarity (ANOSIM). In addition, the trophic group composition of the assemblages for both regions was examined. Results A total of 91 species in 20 families were recorded (GBR, 66 species; GoC, 25 species). Total and habitat species richness were higher on the GBR, whereas biomass was higher in the GoC. No difference in fish density between regions was found. Habitat division among assemblages was greater in the depauperate GoC. Only coral head associations proved to be distinctive on the GBR, whereas three sample groups were found in the GoC (coral heads, horizontal boulders and vertical boulders/rubble). Trophic composition in the two regions was markedly different, with omnivores dominating the GBR fauna and planktivores the GoC. Main conclusions A positive regional–local relationship in fish diversity was found between regions, but fish abundance in both regions remained similar. Contrary to expectations, habitat partitioning, at a community level, was greater in the depauperate GoC. Differences in trophic composition and patterns of habitat use appear to reflect the disparate history of the regions, whereas patterns of abundance may reflect the influence of fundamental relationships between size and abundance in communities. This study highlights the potential of reef faunas to conform to universal numerical trends while maintaining an ability to respond ecologically to local/evolutionary influences. The GoC fauna appears to be exceptionally vulnerable to natural and anthropogenic disturbance owing to the high numerical dominance of habitat‐specific species and to the limited potential for functional redundancy within the system.

Taking species abundance distributions beyond individuals - Hélène Morlon; Ethan P. White; Rampal S. Etienne; Jessica L. Green; Annette Ostling; David Alonso; Brian J. Enquist; Fangliang He; Allen Hurlbert; Anne E. Magurran; Brian A. Maurer; Brian J. McGill; et al. (Ecology Letters, 2009)
The species abundance distribution (SAD) is one of the few universal patterns in ecology. Research on this fundamental distribution has primarily focused on the study of numerical counts, irrespective of the traits of individuals. Here we show that considering a set of Generalized Species Abundance Distributions (GSADs) encompassing several abundance measures, such as numerical abundance, biomass and resource use, can provide novel insights into the structure of ecological communities and the forces that organize them. We use a taxonomically diverse combination of macroecological data sets to investigate the similarities and differences between GSADs. We then use probability theory to explore, under parsimonious assumptions, theoretical linkages among them. Our study suggests that examining different GSADs simultaneously in natural systems may help with assessing determinants of community structure. Broadening SADs to encompass multiple abundance measures opens novel perspectives in biodiversity research and warrants future empirical and theoretical developments.

Participation of HERG channel cytoplasmic structures on regulation by the G protein-coupled TRH receptor - Carlos Alonso-Ron; Francisco Barros; Diego G. Manso; David Gómez-Varela; Pablo Miranda; Luis Carretero; Pedro Domínguez; Pilar de la Peña (Pflügers Archiv - European Journal of Physiology, 2009)

The implicit assumption of symmetry and the species abundance distribution - David Alonso; Annette Ostling; Rampal S. Etienne (Ecology Letters, 2008)
Species abundance distributions (SADs) have played a historical role in the development of community ecology. They summarize information about the number and the relative abundance of the species encountered in a sample from a given community. For years ecologists have developed theory to characterize species abundance patterns, and the study of these patterns has received special attention in recent years. In particular, ecologists have developed statistical sampling theories to predict the SAD expected in a sample taken from a region. Here, we emphasize an important limitation of all current sampling theories: they ignore species identity. We present an alternative formulation of statistical sampling theory that incorporates species asymmetries in sampling and dynamics, and relate, in a general way, the community‐level SAD to the distribution of population abundances of the species integrating the community. We illustrate the theory on a stochastic community model that can accommodate species asymmetry. Finally, we discuss the potentially important role of species asymmetries in shaping recently observed multi‐humped SADs and in comparisons of the relative success of niche and neutral theories at predicting SADs.

Species abundance distributions: moving beyond single prediction theories to integration within an ecological framework - Brian J. McGill; Rampal S. Etienne; John S. Gray; David Alonso; Marti J. Anderson; Habtamu Kassa Benecha; Maria Dornelas; Brian J. Enquist; Jessica L. Green; Fangliang He; Allen H. Hurlbert; Anne E. Magurran; et al. (Ecology Letters, 2007)
Species abundance distributions (SADs) follow one of ecology’s oldest and most universal laws – every community shows a hollow curve or hyperbolic shape on a histogram with many rare species and just a few common species. Here, we review theoretical, empirical and statistical developments in the study of SADs. Several key points emerge. (i) Literally dozens of models have been proposed to explain the hollow curve. Unfortunately, very few models are ever rejected, primarily because few theories make any predictions beyond the hollow‐curve SAD itself. (ii) Interesting work has been performed both empirically and theoretically, which goes beyond the hollow‐curve prediction to provide a rich variety of information about how SADs behave. These include the study of SADs along environmental gradients and theories that integrate SADs with other biodiversity patterns. Central to this body of work is an effort to move beyond treating the SAD in isolation and to integrate the SAD into its ecological context to enable making many predictions. (iii) Moving forward will entail understanding how sampling and scale affect SADs and developing statistical tools for describing and comparing SADs. We are optimistic that SADs can provide significant insights into basic and applied ecological science.

A dispersal‐limited sampling theory for species and alleles - Rampal S. Etienne; David Alonso (Ecology Letters, 2005)

Competition and introduction regime shape exotic bird communities in Hawaii - Javier G.P. Gamarra; Jos M. Montoya; David Alonso; Ricard V. Sol (Biological Invasions, 2005)

Effects of Trochanteric Soft Tissues and Bone Density on Fracture of the Female Pelvis in Experimental Side Impacts - Brandon S. Etheridge; David P. Beason; Robert R. Lopez; Jorge E. Alonso; Gerald McGwin; Alan W. Eberhardt (Annals of Biomedical Engineering, 2005)

Sampling Hubbell's neutral theory of biodiversity - David Alonso; Alan J. McKane (Ecology Letters, 2004)
In the context of neutral theories of community ecology, a novel genealogy‐based framework has recently furnished an analytic extension of Ewens’ sampling multivariate abundance distribution, which also applies to a random sample from a local community. Here, instead of taking a multivariate approach, we further develop the sampling theory of Hubbell's neutral spatially implicit theory and derive simple abundance distributions for a random sample both from a local community and a metacommunity. Our result is given in terms of the average number of species with a given abundance in any randomly extracted sample. Contrary to what has been widely assumed, a random sample from a metacommunity is not fully described by the Fisher log‐series, but by a new distribution. This new sample distribution matches the log‐series expectation at high biodiversity values ( θ > 1) but clearly departs from it for species‐poor metacommunities ( θ

Novel stop and frameshifting mutations in the autosomal dominant polycystic kidney disease 2 (PKD2) gene - Miguel Viribay; Tomohito Hayashi; Dolores Tellería; Toshio Mochizuki; David M. Reynolds; Rafael Alonso; Xose M. Lens; Felipe Moreno; Peter C. Harris; Stefan Somlo; José L. San Millán (Human Genetics, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)